10 Years of Quality Management: Perception and Importance from GPs' Point of View - Kühlein, Thomas; Madlo-Thiess, F.; Wambach, V.; Schaffer, Susann (Gesundheitswesen, 2018)
BACKGROUND: Quality management (QM) became mandatory for the ambulatory sector of the German health care system 10 years ago. OBJECTIVES: The aim of this study was to find out how general practitioners (GPs) perceived the introduction of this measure, how they see it today and what they expect of the future concerning QM. MATERIALS AND METHODS: In a qualitative study, interviews following a semi-structured guideline with GPs were conducted. Following transcription, interviews were coded in triangulation, first inductively, then deductively until saturation was reached. Main topics and code families were agreed on after discussion. RESULTS: There was consensus on the necessity of standardization of basic processes like hygiene. However, the application of QM to an activity that emphasizes personal relationships and communication was seen as barely possible. GPs stated that they reduced QM to a tolerable and for them reasonable minimum. GPs mostly refused certification. The next 10 years were seen with pessimism in terms of more bureaucratic guidelines. CONCLUSION: The statutory introduction of QM was an attack on medical professionalism. Instead of passive resistance and reduction of QM to a minimum, engaged independent quality work might help to regain the trust of society we seem to have lost and restore the professional autonomy we need for our work.
EVALuna2:33834

Active monitoring of adverse reactions following COVID-19 and other vaccinations: a feasibility study as part of the CoVaKo project - Zeschick, Nikoletta; Warkentin, Lisette; Kühlein, Thomas; Steininger, Philipp; Überla, Klaus; Hueber, Susann; Sebastiao, Maria (Pilot and Feasibility Studies, 2022)
Background: The Corona-Vakzin-Konsortium project (CoVaKo) analyses the efficacy and safety of COVID-19 vaccines in a real-world setting, as well as breakthrough infections in Bavaria, Germany. A subproject of CoVaKo aims to identify adverse reactions of the COVID-19 vaccine and compare these to adverse reactions of other vaccines in an online survey. In a preceding feasibility study, the study materials were tested for comprehensibility, visual design, and motivation to participate, as well as for their ability to be implemented and carried out in primary care practices and vaccination centres. Methods: We used a mixed-methods research design. First, three focus groups consisting of general population participants were organised to evaluate the study materials and survey. Second, a test roll-out was conducted in vaccination centres and primary care practices that involved implementing and quantitatively evaluating the online survey. Third, interviews were conducted with participating general practitioners and heads of vaccination centres four weeks after the test roll-out. Results: Parts of the information and registration form proved incomprehensible, specifically regarding the recruitment material and/or online survey. For example, headings were misleading given that, relative to other vaccinations, the COVID-19 vaccination was overemphasised in the title. Participants requested additional information regarding the procedure and completion time. Within 31 days, 2199 participants, who received either a COVID-19 vaccination (99%) or at least one of the control vaccinations (1%), registered for the study. Participants (strongly) agreed that the registration process was easy to understand, that the completion time was reasonable, and that the technical setup was straightforward. Physicians and heads of the vaccination centres perceived the study as easy to integrate into their workflow. The majority expressed willingness to participate in the main study. Conclusions: Our study indicated that identifying and documenting adverse reactions following vaccinations using an online survey is feasible. Testing materials and surveys provided valuable insight, enabling subsequent improvements. Participation from health professionals proved essential in ensuring the practicality of procedures. Lastly, adapting the study’s organisation to external fluctuating structures and requirements confirmed necessary for a successful implementation, especially due to dynamic changes in the nation’s COVID-19 vaccination strategies. Trial registration: The trial was retrospectively registered at the “Deutsches Register Klinischer Studien” (DRKS-ID: DRKS00025881) on Oct 14, 2021.
CRIS-Team Scopus Importer:2022-07-15
Keywords: Adverse reactions; COVID-19; General practitioners; Healthcare staff; Online survey; Vaccination; Vaccination centres

Analysis of morbidity and health care usage of patients with suspected thyroid disorders - Tomandl, Johanna; Hafner, Lucas; Biermann, Valeria; Tauchmann, Harald; Schöffski, Oliver; Kühlein, Thomas; Hueber, Susann (Preventing Overdiagnosis Congress 2019, 2019)
Objectives (150 words) In many countries the incidence of thyroid cancer increased in the last years, while thyroid cancer mortality remained stable. This is seen as an indicator for overdiagnosis. Furthermore, many surgically removed thyroid nodules turn out to be benign, especially in Germany. Germany has a highly fragmented health care system with easy access to diagnostic imaging even at the level of general practice. Most thyroid nodules are detected using sonography early in the work-up of suspected thyroid disorders, which might trigger control loops and invasive treatment. Thus, the objective of this study is to systematically analyze whether the early use of sonography in the work-up of suspected thyroid disease might lead in a cascade effect from overdiagnosis to overtreatment. The following research question will be answered: What effects does the early use of sonography in the diagnostic process of suspected thyroid disorders have on morbidity, health care utilization and costs? Method (150 words) To answer this research question a retrospective cohort-study design comparing two propensity-matched groups was chosen. Claims data of patients with statutory health insurance held by the Bavarian Association of Statutory Health Insurance Physicians were used. Early use of sonography was defined as having an initial TSH test followed by a sonography within 28 days. Patients having received a TSH test in 2012 were included and allocated to one of the two following groups: Group 1: TSH test followed by sonography of the thyroid within 28 days. Group 2: TSH test without sonography of the thyroid within 28 days. The two groups were matched for sociodemographic characteristics, morbidity, and reason for encounter using propensity score matching. The two groups are currently compared in terms of morbidity, health care utilization and costs. Results (150 words) After propensity score matching, the sample consisted of 68,862 patients in each group. Data analysis is not completed yet. The results will be available for presentation until the conference. Conclusions (150 words) Early use of sonography in the work-up of suspected thyroid disorders might trigger a cascade of overdiagnosis and overtreatment. By systematically analyzing clinical pathways of patients with suspected thyroid disorders and the resulting medical and economic consequences, we hope to contribute to the identification and reduction of overdiagnosis and overtreatment concerning thyroid disorders. The project is embedded in the PRevention of Overdiagnosis in PRImary CARE (PRO PRICARE) research network funded by the German Federal Ministry of Research and Education. </

A qualitative interpretation of challenges associated with helping patients with multiple chronic diseases identify their goals - Kühlein, Thomas; et al. (Journal of Comorbidity, 2016)
BACKGROUND: Patients with multiple chronic diseases are usually treated according to disease-specific guidelines, with outcome measurements focusing mostly on biomedical indicators (e.g. blood sugar levels or lung function). However, for multimorbidity, a goal-oriented approach focusing on the goals defined by the individual patient, may be more suitable. Despite the clear theoretical and conceptual advantages of including patient-defined goals in clinical decision-making for multimorbidity, it is not clear how patients define their goals and which aspects play a role in the process of defining them. OBJECTIVE: To explore goal-setting in patients with multimorbidity. DESIGN: Qualitative analysis of interviews with 19 patients diagnosed with chronic obstructive pulmonary disease and comorbidities. RESULTS: Patients do not naturally present their goals. Their goals are difficult to elicit, even when different interviewing techniques are used. Four underlying hypotheses which may explain this finding were identified from the interviews: (1) patients cannot identify with the concept of goal-setting; (2) goal-setting is reduced due to acceptation; (3) actual stressors predominate over personal goal-setting; and (4) patients may consider personal goals as selfish. CONCLUSIONS: Our findings advocate for specific attention to provider skills and strategies that help patients identify their personal goals. The hypotheses on why patients may struggle with defining goals may be useful to prompt patients in this process and support the development of a clinical method for goal-oriented care.
EVALuna2:33550

Association of mental health, quality of life, and SARS-CoV-2 infection in individuals in need of care: Results from a multicentre registry study - Lukaschek, Karoline; Hentschel, Heidi; Rottenkolber, Marietta; Alberer, Martin; Winter, Susanne; Sebastiao, Maria; Arend, Florian; Dreischulte, Tobias; Gágyor, Ildikó; Hausen, Anita; Hoelscher, Michael; Janke, Christian; et al. (PLoS ONE, 2025)
Objective Investigating the association between mental health, quality of life, and SARS-CoV-2 infection in individuals in need of care compared to independent living individuals. Individuals in need of care include both care home residents and those receiving care either through an outpatient care service or from family members. Methods This cross-sectional study assessed symptoms of depression (PHQ-9>9) and anxiety (GAD-7>9), quality of life (EQ-5D-5L, EQ-VAS), dementia (SIS), SARSCoV-2 infection and socio-demographic variables in the total sample (N=978, 64.4% female, mean age: 77.5±13.8 years) and subgroups (study group, STG, n=532, individuals in need of care, SARS-CoV-2 positive; control group 1, CG1, n=213, individuals in need of care, SARS-CoV-2 negative; control group 2, CG2, n=233, independent living individuals, SARS-CoV-2 positive). Multivariate logistic regressions were performed. Results Depressive symptoms (PHQ-9>9) were significantly associated with lower quality of life in the total sample (EQ-VAS: OR 0.96, 95% CI 0.95-0.97, p<0.001; EQ-5D-5L: OR 0.14, 95% CI 0.07-0.29, p<0.001) and across all subgroups. Anxiety (GAD-7>9) was significantly associated with lower quality of life in the total sample (EQ-VAS: OR 0.97, 95% CI 0.95-0.98, p<0.001; EQ-5D-5L: OR 0.19, 95% CI 0.08-0.50, p<0.001) and all subgroups except CG1. In individuals in need of care with COVID-19, depressive symptoms were additionally associated with symptomatic infection (OR 3.47, 95% CI 1.45-8.28, p=0.005). Conclusion Depression and anxiety were significantly associated with reduced quality of life, irrespective of living environment or SARS-CoV-2 infection status, underscoring the need for targeted mental health interventions in older adults. While our model explained a considerable portion of the variability in depression and anxiety, further research is needed to account for the remaining proportion.
CRIS-Team Scopus Importer:2025-05-23

Associations of Mental Health Issues with Health Literacy and Vaccination Readiness against COVID-19 in Long-Term Care Facilities—A Cross-Sectional Analysis - Sanftenberg, Linda; Gschwendner, Maresa; Grass, Andreas; Rottenkolber, Marietta; Zöllinger, Isabel; Sebastiao, Maria; Kühlein, Thomas; Hindenburg, Dagmar; Gágyor, Ildikó; Wildgruber, Domenika; Hausen, Anita; Janke, Christian; et al. (European Journal of Investigation in Health, Psychology and Education, 2024)
Vaccinations against COVID-19 are of the utmost importance in long-term care facilities. During the pandemic, mental health issues increased significantly. This cross-sectional analysis aimed to assess the associations of depression and anxiety with health literacy in people in need of care and the association of depression and burnout with vaccination readiness against COVID-19 in health care workers (HCWs). Within our cross-sectional study, people in need of care were assessed for symptoms of depression (PHQ-9), anxiety (GAD-7), and health literacy (HLS-EU-Q16). Among HCWs, we assessed symptoms of depression (PHQ-9) and burnout (MBI-HSS), as well as psychological antecedents of vaccination (5C) to measure vaccination readiness against COVID-19. A multivariate regression analysis was performed. Symptoms of a major depression were significantly associated with reduced health literacy (p = 0.010) in people in need of care. Among HCWs, symptoms of depression and burnout reduced vaccination readiness against COVID-19 significantly. In particular, collective responsibility was reduced in HCWs suffering from burnout symptoms (p = 0.001). People in need of care and their HCWs could benefit from intensified target group-specific vaccination counseling. Additionally, more attention should be paid to the protection of mental health in long-term care facilities.
CRIS-Team Scopus Importer:2024-04-05
Keywords: COVID-19 pandemic; health literacy; healthcare workers; mental health; people in need of care; vaccination readiness

Associations of mental health with vaccination readiness in informal caregivers and the vaccination status of their care recipients during the Covid-19 pandemic – A cross sectional analysis - Sanftenberg, Linda; Bader, Felix; Rottenkolber, Marietta; Sebastiao, Maria; Kühlein, Thomas; Eidenschink, Christine; Gágyor, Ildikó; Wildgruber, Domenika; Hausen, Anita; Janke, Christian; Hoelscher, Michael; Teupser, Daniel; et al. (Vaccine, 2024)
Introduction: Vaccinations are important for informal caregivers and their care recipients. Mental health problems are common among care givers. The aim of this study was to investigate vaccination readiness in informal caregivers and associations with mental health issues. Associations between vaccination readiness in informal caregivers and the vaccination status of their aged care recipients were examined. Methods: Within the multicenter prospective registry study ‘Bavarian ambulatory Covid-19 Monitor (BaCoM) ‘, informal caregivers were asked for symptoms of depression (PHQ-9), burden of caretaking (BSFC-s), psychological antecedents of vaccination readiness (5C model) and previous Covid-19 infections of their care recipients. The vaccination status against Covid-19, seasonal influenza and pneumococcal disease was determined via vaccination certificates. Data analysis was performed using ordinal regressions and Mann-Whitney-U tests. Results: Data of n = 91 informal caregivers, associated with n = 84 care recipients were collected. Symptoms of depression were associated with reduced vaccination readiness (Calculation: p = 0.026, OR = 1.18), as well as the perceived burden of caretaking (Confidence: p = 0.006, OR = 0.88). A previous Covid-19 infection of the care recipients was associated with decreased vaccination readiness of informal caregivers (Median (Q1–Q3) Confidence: 5.0 (4.5–6.0) vs. 4.0 (3.0–5.0); Calculation: 5.0 (3.0–6.0) vs. 4.0 (1.0–5.0)). The vaccination status of the care recipients interrelated significantly with vaccination readiness of their informal caregivers (Confidence: p < 0.001; Complacency: p < 0.01; Constraints p < 0.05). No significant interrelations between vaccination readiness and the vaccination status against seasonal influenza or pneumococcal disease occurred. Conclusion: Mental health issues of informal caregivers seem to be associated with the actual vaccination status against Covid-19 in their care recipients. Target group specific counselling as well as an active involvement of informal caregivers in shared decision-making processes can be of relevance, but even more attention should be paid to the protection of mental health for informal caregivers. Trial registration number: German Register of Clinical Studies DRKS 26039.
CRIS-Team Scopus Importer:2024-09-06
Keywords: COVID-19; Informal caregivers; Long-term care; Mental health; Vaccination readiness

Asynchronous, digital teaching in times of COVID-19: a teaching example from general practice - van der Keylen, Piet; Lippert, Nikoletta; Kunisch, Raphael; Kühlein, Thomas; Roos, Marco (GMS Journal for Medical Education, 2020)
Background: The SARS-CoV-2 pandemic had a strong impact on academic teaching and could change it sustainably. Ad hoc digitization of teaching had to be carried out.
CRIS-Team WoS Importer:2021-01-08

Auswirkungen eines Wahlfachs zur evidenzbasierten klinischen Entscheidungsfindung auf die Kompetenzen und Einstellungen von Medizinstudierenden: Eine Pilotstudie - Lippert, Nikoletta; Frank, Luca; Schnitzius, Kathrin; Stubner, Birgit Maria; Kühlein, Thomas; Roos, Marco; van der Keylen, Piet (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2021)
Background: Evidence-based medicine (EbM) as a teaching subject is increasingly taken into account in the Master Plan 2020. To date, neither theoretical requirements nor practical applications of EbM have been consistently implemented in the clinical curriculum. To fill this gap, a digital and tutor-based EbM course has been developed. The aim is to identify the student characteristics (statistical competence, Need for Cognition (NFC), work and experience patterns (AVEM), diagnostic uncertainty) of the first cohort in order to ensure successful course implementation and to prepare future doctors for their role as mediators of health literacy using EbM methods. Methods: The long-term study started in the summer term 2019 with 10 medical students during their clinical training. The measurements were conducted before (t0) and after course attendance (t1). Socio-demographic variables were taken at t0, the Quick Risk Test, PRU questionnaire, the NFC scale and the AVEM were collected at t0 and t1. Results: Half of the students started their doctoral thesis before attending the course. The first test results of the Quick Risk Test (t0) were between 50 % and 90 % and at t1 between 60 % and 100 %. The students showed high scores on the NFC scale (X¯ = 4.6, SD = 0.52, Δ X¯ t0 - t1 = 0.1) and medium scores on the Perfectionism scale (X¯ = 3.8, SD = 0.51, Δ X¯ t0 - t1 = 0.1), Resignation Tendency (X¯ = 3.8, SD = 1.17, Δ X¯ t0 - t1 = 0.1) and on the scale Aggressive Problem Solving (X¯ = 3.9, SD = 1.06, Δ X¯ t0 - t1 = 0.2). They achieved high levels of Anxiety Due to Diagnostic Uncertainty (X¯ = 4.8, SD = 0.69, Δ X¯ t0 - t1 = 0.4) and on the scale Concern about Poor Outcomes (X¯ = 3.9, SD = 1.54, Δ X¯ t0 - t1 = 0.6). The scale Restraint in Disclosing Uncertainty to Patients was more pronounced than the scale Restraint in Disclosing Errors to Physicians (X¯ = 3.5, SD = 0.93, Δ X¯ t0 - t1 = -0.3 compared to X¯ = 2.3, SD = 1.20, Δ X¯ t0 - t1 = 0.1). Discussion: Statistical competence improved with course attendance, with only one student being able to correctly answer all items at t1. NFC and AVEM were strongly expressed and were not very sensitive to change in the sample. The greatest changes were observed on the scales of concern about poor results and fear of diagnostic uncertainty, both of which decreased with course participation. Conclusion: In the long term, the development of a new measuring instrument to assess EbM competencies instead of the Quick Risk Test is conceivable. The longitudinal design will also enable us to make causal interpretations and to track changes in students’ competence feelings, behaviour and attitudes.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Decision-making; Evidence-based medicine; Health literacy; Physicians’ reaction to uncertainty; Quick Risk Test

Baby Boom, Pill Break and our big Problem: demographic Change Can we still afford to be Side by Side and against each other? - Kühlein, Thomas; Blumenthal, Sandra (Gesundheitswesen, 2021)
CRIS-Team WoS Importer:2021-12-24

Barriers to practicing General Practice in rural areas - Results of a qualitative pre-post-survey about medical students during their final clinical year - Ludwig, Kathrin; Machnitzke, Corina; Kühlein, Thomas; Roos, Marco (GMS Journal for Medical Education, 2018)
Objective: At the end of the Practical Year (PY), medical students decide on a specialization. Individual motivational factors and barriers play a central role in the choice of the subsequent subject area and the place of establishment (city/country). The aim of this study was to document the barriers of PY students within the General Practice (GP) tertiary elective over time. Methodology: Two guided interviews were conducted with each participant (N=19) as part of qualitative process monitoring - a pre-interview at the start and a post-interview after completion of the PY. Evaluation of the interviews was based on Grounded Theory. Results: 13 barriers could be deduced from the 38 interviews. The most frequently cited barriers were "expected workload", "recreational opportunities", "work-life balance" and "compatibility with family". 13 of the participants were firmly committed to continuing GP training, 12 of whom aspired to opening a practice in a rural area. Another three were considering GP training, three had decided against it after the PY. After the PY, some of the previously anticipated individual barriers were now perceived in a more differentiated manner as a result of practical experience. The barriers "work-life-balance", "compatibility with family", "recreational opportunities" and "infrastructure" had been largely eliminated. Conclusion: The PY General Practice Tertiary itself appears to have a positive impact on the individual barriers expressed before the PY. Targeted experience with a PY in General Practice at the end of study seems to be a solution to increase the attractiveness of the subject.
EVALuna2:34939

Chapter Primary Prevention: Calcium, Vitamin D and K, Nutrition, Physical Activity Kapitel Basistherapie: Kalzium, Vitamin D und K, Ernährung, Körperliches Training - Maus, Uwe; Kühlein, Thomas; Jakob, Franz; Belavy, Daniel; Thomasius, Friederike (Osteologie, 2023)
This article presents the current status of the DVO guideline recommendations on basic therapy. Basic therapy is the foundation of any osteoporosis management and is also vital to its primary prevention; even before bone mineral density is low, or fractures occur. Based on an updated literature review, the chapter covers recommendations on calcium, vitamin D, vitamin K and other nutritional aspects as well as physical activity. Previous recommendations were reviewed and amended based on the new literature. Recommendations on calcium and vitamin D intake, through diet or supplements, remain unchanged. Vitamin K is recommended only to compensate for a deficiency, since data are too inconsistent for a recommendation in other settings such as fracture prevention. Physical activity has a positive effect on fracture risk and bone mineral density and therefore continues to be an important recommendation, also recommended, ideally in an appropriate supervised training program.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Calcium; exercise; Osteoporosis; vitamin d; vitamin K

Checklisten in der Hausarztpraxis – eine Entwicklungsstudie mit Vorher/Nachher-Vergleich - Saggau, Korbinian; Höfle, Anina; Schedlbauer, Angela; Hueber, Susann; Roos, Marco; Kühlein, Thomas; Heinmüller, Stefan (Zeitschrift für Allgemeinmedizin, 2021)
Background Quality assurance in Germany focuses on support processes (requirements of hygiene etc.) rather than on quality of care (QOC). Systems that do focus on QOC are referred to as “clinical governance” (CG). We understand CG as a process of professional self-reflection and management. An electronic checklist (eCL) for Chronic Obstructive Lung Disease (COPD) was developed reminding doctors of important aspects of care, assuring adequate documentation, and generating data at the same time. We describe the development of the eCL and a before/ after analysis of process-QOC for COPD-patients in a single group family practice. Methods Developmental study with a before/after-analysis. To capture QOC at baseline (t0) electronic health records (EHR) of COPDpatients were surveyed using a guideline-based questionnaire. Our intervention was an eCL, which can be used within the EHR. Doctors and practice assistants were trained in the application of the eCL, its use remained optional. One year (t1) and four years (t2) after implementation QOC was reanalysed. Results At t0 103 COPD patients were identified. For 58% a spirometry was documented. Smoking status was recorded in 56% and 34% were vaccinated against influenza. After introduction of the eCL due to some changes in the practice 80 patients at t1 and 49 patients at t2 were identified. For 71% (t1) and 63% (t2) a spirometry was documented. Smoking status was documented in 75% (t1) and 90% (t2). Influenza vaccination was documented in 33% (t1) and 55% (t2) of patients. Conclusions Development and implementation of an eCL in the setting of our office within the EHR was possible. Our results indicate that the provision of an eCL together with a short introduction can help improve QOC. The eCL allows doctors to perform CG autonomously.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Checklist; Chronic disease; Evidence-based medicine; Family medicine; General practice

Coding in general practice-Will the ICD-11 be a step forward? - Kühlein, Thomas; Virtanen, Martti; Claus, Christoph; Popert, Uwe; Van Boven, Kees (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2018)
Primary care physicians in Germany don't benefit from coding diagnoses-they are coding for the needs of others. For coding, they mostly are using either the thesaurus of the German Institute of Medical Documentation and Information (DIMDI) or self-made cheat-sheets. Coding quality is low but seems to be sufficient for the main use case of the resulting data, which is the morbidity adjusted risk compensation scheme that distributes financial resources between the many German health insurance companies.Neither the International Classification of Diseases and Health Related Problems (ICD-10) nor the German thesaurus as an interface terminology are adequate for coding in primary care. The ICD-11 itself will not recognizably be a step forward from the perspective of primary care. At least the browser database format will be advantageous. An implementation into the 182 different electronic health records (EHR) on the German market would probably standardize the coding process and make code finding easier. This method of coding would still be more cumbersome than the current coding with self-made cheat-sheets.The first steps towards a useful official cheat-sheet for primary care have been taken, awaiting implementation and evaluation. The International Classification of Primary Care (ICPC-2) already provides an adequate classification standard for primary care that can also be used in combination with ICD-10. A new version of ICPC (ICPC-3) is under development. As the ICPC-2 has already been integrated into the foundation layer of ICD-11 it might easily become the future standard for coding in primary care. Improving communication between the different EHR would make taking over codes from other healthcare providers possible. Another opportunity to improve the coding quality might be creating use cases for the resulting data for the primary care physicians themselves.
EVALuna2:34418

Consequences of early thyroid ultrasound on subsequent tests, morbidity and costs: an explorative analysis of routine health data from German ambulatory care - Hueber, Susann; Biermann, Valeria; Tomandl, Johanna; Warkentin, Lisette; Schedlbauer, Angela; Tauchmann, Harald; Klemperer, David; Lehmann, Maria; Donnachie, Ewan; Kühlein, Thomas (BMJ Open, 2023)
Objectives This study aims to evaluate whether the use of thyroid ultrasound (US) early in the work-up of suspected thyroid disorders triggers cascade effects of medical procedures and to analyse effects on morbidity, healthcare usage and costs. Study design Retrospective analysis of claims data from ambulatory care (2012-2017). Setting Primary care in Bavaria, Germany, 13 million inhabitants. Participants Patients having received a thyroid stimulating hormone (TSH) test were allocated to (1) observation group: TSH test followed by an early US within 28 days or (2) control group: TSH test, but no early US. Propensity score matching was used adjusting for socio-demographic characteristics, morbidity and symptom diagnosis (N=41 065 per group after matching). Primary and secondary outcome measures Using cluster analysis, groups were identified regarding frequency of follow-up TSH tests and/or US and compared. Results Four subgroups were identified: cluster 1: 22.8% of patients, mean (M)=1.6 TSH tests; cluster 2: 16.6% of patients, M=4.7 TSH tests; cluster 3: 54.4% of patients, M=3.3 TSH tests, 1.8 US; cluster 4: 6.2% of patients, M=10.9 TSH tests, 3.9 US. Overall, reasons that explain the tests could rarely be found. An early US was mostly found in clusters 3 and 4 (83.2% and 76.1%, respectively, were part of the observation group). In cluster 4 there were more women, thyroid-specific morbidity and costs were higher and the early US was more likely to be performed by specialists in nuclear medicine or radiologists. Conclusion Presumably unnecessary tests in the field of suspected thyroid diseases seem to be frequent, contributing to cascades effects. Neither German nor international guidelines provide clear recommendations for or against US screening. Therefore, guidelines on when to apply US and when not are urgently needed.
CRIS-Team Scopus Importer:2023-03-24
Keywords: PRIMARY CARE; Thyroid disease; ULTRASONOGRAPHY

Consultation skills training as an element of general practice training in Germany - a qualitative survey - Nittritz, Christine; Schaffer, Susann; Kühlein, Thomas; Roos, Marco (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2016)
INTRODUCTION: The consultation is at the heart of general practice. It is the central setting through which primary care is delivered. The competency requirements are laid down internationally by competency-based curricula for undergraduate and postgraduate education. So far, there is no competency-based vocational training to develop consultation skills in general practice in Germany. The study describes experiences with consultation skills training as an element of general practice training as reported by trainees and trainers in Germany. METHODS: A qualitative and exploring approach was chosen because there is little experience with the German situation. We conducted structured focus group interviews with trainees and trainers, respectively. We recruited all participants by e-mail via the mail distributor "Junge Allgemeinmedizin Deutschland" (JADE, a trainee and junior GP organization) and the academic teachers of the Friedrich-Alexander University Erlangen-Nürnberg. Altogether, four focus group interviews with three to five participants were conducted, varying in length from 25 to 65minutes. All interviews were recorded digitally and transcribed verbatim. Then a qualitative content analysis was performed. RESULTS: The statements of the ten trainees and five trainers mapped a system of four main categories: (a) association with the term consultation, (b) parts of a consultation, (c) competencies required for professional practice, (d) consultation skills training as an element of vocational training. Overall, all participants regarded the consultation as the most important element in general practice. Important content of consultations is to build a relationship with the patient, gather information, conduct physical examinations and achieve informed consent on further proceedings. All participants agreed that physicians need different sets of competencies: medical expertise, communication skills, examination skills and professionalism. Finally, there was a broad consensus that a competency-based general practice training to support the development of consultation skills is lacking in Germany. The majority acknowledged the need for change. CONCLUSION: So far, the consultation skills development within the general practice training in Germany is regarded as deficient. Both trainees and trainers have stressed the importance of change in vocational training. With the new competency-based curriculum for general practice in Germany and the associated development of supporting tools important prerequisites have been provided.
EVALuna2:33547

Controlling Prescribing through “Preferred Drug” Targets—The Bavarian Experience - Gollnick, Julia; Zeschick, Nikoletta; Muth, Julia; Hörbrand, Franziska; Behnke, Kerstin; Killian, Peter; Sebastiao, Maria; Kühlein, Thomas; Donner-Banzhoff, Norbert (International Journal of Environmental Research and Public Health, 2024)
Background: The rising costs of drugs are putting health care systems under pressure. We report on the Bavarian Drug Agreement, which employs prescribing targets for preferred and generic drugs in ambulatory care. Under this agreement, providers are regularly profiled with individual feedback but also possible sanctions. We investigated the degree to which targets were being met (or not) and why failure occurred. Methods: We analysed prescribing data aggregated by practice for the quarter 1/2018. We chose eight specialisation groups and analysed their drug targets with a high prescribing volume, widely missed drug targets (<90%), and drugs preventing drug target achievement. Characterisation of drug targets and preventing drugs was undertaken. Results: Drug targets with a high prescribing volume are mostly achieved, while highly missed drug targets mostly do not affect the main indication area of the specialisation groups considered. Generic drug targets seem to be more easily achieved than recommended drug targets. Paediatrics accounts for the largest number of missed drug targets. Conclusions: The Bavarian tool implemented uses the prescribing volume (DDD) and price components to evaluate the prescription behaviour of physicians. Well-established drugs with demonstrated effectiveness, safety, and lower costs are preferred. Nevertheless, me-too drugs, combination drugs, costly innovations with unclear value, and drugs with application methods of variable convenience challenge the drug prescribers and are reasons for missed drug targets.
CRIS-Team Scopus Importer:2024-10-11
Keywords: ambulatory care/economics; budgets; cost control/trends; drug prescriptions; drug therapy/economics; drug therapy/trends

Detecting Medication Risks among People in Need of Care: Performance of Six Instruments - Dreischulte, Tobias; Sanftenberg, Linda; Hennigs, Philipp; Zöllinger, Isabel; Schwaiger, Rita; Floto, Caroline; Sebastiao, Maria; Kühlein, Thomas; Hindenburg, Dagmar; Gagyor, Ildikó; Wildgruber, Domenika; Hausen, Anita; et al. (International Journal of Environmental Research and Public Health, 2023)
Introduction: Numerous tools exist to detect potentially inappropriate medication (PIM) and potential prescribing omissions (PPO) in older people, but it remains unclear which tools may be most relevant in which setting. Objectives: This cross sectional study compares six validated tools in terms of PIM and PPO detection. Methods: We examined the PIM/PPO prevalence for all tools combined and the sensitivity of each tool. The pairwise agreement between tools was determined using Cohen’s Kappa. Results: We included 226 patients in need of care (median (IQR age 84 (80–89)). The overall PIM prevalence was 91.6 (95% CI, 87.2–94.9)% and the overall PPO prevalence was 63.7 (57.1–69.9%)%. The detected PIM prevalence ranged from 76.5%, for FORTA-C/D, to 6.6% for anticholinergic drugs (German-ACB). The PPO prevalences for START (63.7%) and FORTA-A (62.8%) were similar. The pairwise agreement between tools was poor to moderate. The sensitivity of PIM detection was highest for FORTA-C/D (55.1%), and increased to 79.2% when distinct items from STOPP were added. Conclusion: Using a single screening tool may not have sufficient sensitivity to detect PIMs and PPOs. Further research is required to optimize the composition of PIM and PPO tools in different settings.
CRIS-Team Scopus Importer:2023-02-24
Keywords: adverse drug reaction; inappropriate medication; nursing home residents; polypharmacy; prescribing omission

Development of a self-assessment tool to address the functioning of community-dwelling older adults in general practice: a validation study of the EFA23 questionnaire - Rink, Laura; Floto, Caroline; Apel, Katharina; Weiss, Maren; Stegmeier, Elmar; Kühlein, Thomas; Sebastiao, Maria (BMC Primary Care, 2024)
Background: Multimorbidity is increasingly prevalent among ageing patients, leading to reduced daily functioning. To address the challenges posed by multimorbidity in older adults, a person- and context-centred approach is needed. This study aimed to develop a questionnaire as a self-assessment tool for older adults focusing on functioning in general practice based on the International Classification of Functioning, Disability and Health (ICF). Methods: A mixed-methods approach was employed in the development and validation of the German EFA23 (Erfassung Funktionaler Gesundheit im Alter – 23 Fragen; Assessing Functional Health in Old Age – 23 questions) questionnaire. Based on an ICF subset developed in a preparatory phase and consensus study, questionnaire items were formulated and tested in a qualitative pretest, followed by a validation study. A workshop with general practitioners (GPs) was held to develop a supplementary manual for GPs on how to interpret the questionnaire results and discuss them with the patients. Results: A total of 69 items were developed and tested in the qualitative pretest with 15 respondents, resulting in 37 items for the validation study. The validation study, involving 237 older adults, showed the presence of one significant principal component. It demonstrated good internal consistency (Cronbach’s alpha = 0.967) and construct validity, showing positive correlations with established assessment tools. Descriptive statistics showed differences between the means of self-assessment by patients and an external GP assessment. The final EFA23 questionnaire consists of 23 items assessing limitations in functioning. Conclusions: The EFA23 questionnaire can be used as a valid self-assessment instrument to measure functioning in older adults, supporting a person- and context-centred approach in general practice.
CRIS-Team Scopus Importer:2024-08-09
Keywords: Functional health; General practice; International classification of functioning; Multimorbidity; Older adults

Development of a subset of the international classification of functioning, disability and health as a basis for a questionnaire for community-dwelling older adults aged 75 and above in primary care: a consensus study - Rink, Laura; Tomandl, Johanna; Womser, Sonja; Kühlein, Thomas; Sebastiao, Maria (BMJ Open, 2023)
Objectives Functioning of older adults needs to be adequately described before it can become the focus of care. The International Classification of Functioning, Disability and Health (ICF) provides a basis for describing functioning. As the ICF is too extensive for daily practice in primary care, there is a need for a reduced number of categories. The aim is to develop an ICF-subset for community-dwelling older adults aged 75 and above in primary care. Design The scientific basis for decision-making in our consensus study was laid by four preparatory studies, identifying potentially relevant ICF categories from four perspectives (research, patients', experts' and clinical perspective). The results of the preparatory phase were discussed by an international expert panel in a consensus study following the Nominal Group Technique (NGT). Setting An international 1-day online consensus conference. Participants International experts (n=7) participated in the consensus conference, meeting the following criteria: extensive expertise in the field of the ICF and/or caring for older adults, and being fluent in English. Results Each preparatory study yielded a different number of categories with some overlaps but also differences. The expert panel decided to: (1) restrict the subset to second-level categories and reduce the number of categories from the preparatory phase, (2) limit the subset to the component activities and participation and (3) weight the patients' perspective as the most relevant one. Conclusions By using consensus techniques and the NGT, the process led to 51 second-level ICF categories to describe the functioning of community-dwelling older adults. The decisions made in the consensus conference emphasised the importance of considering the individual life situation from a more holistic perspective and addressing functioning as a focus of care. Next, the 51 categories will contribute to the development of an ICF-based questionnaire.
CRIS-Team Scopus Importer:2023-09-15
Keywords: decision making; geriatric medicine; primary care; qualitative research

Differences between the antibiotic prescribing pattern of newly arrived refugees in Germany and the German population - Kahl, Fabian; Kühlein, Thomas (Conflict and Health, 2018)
The number of refugees arriving in Europe increased dramatically in 2015, challenging the German health system. Amongst others, the treatment of infectious diseases is an important topic in refugee healthcare. A high prevalence of multi-drug-resistant organisms has been identified among the refugee population. Still, little is known about the prescription of antibiotic medication for refugees. We conducted a descriptive analysis of all antibiotics prescribed to newly arrived refugees who were treated as outpatients between 10/01/2014 and 09/30/2015 in Erlangen, an average sized German town. The City's invoicing documents were used to collect data on prescriptions written for refugees. Basic penicillins, aminopenicillins with beta-lactamase inhibitor and cephalosporins constituted the largest proportion of antibiotics prescribed in the adult refugee group. Of these, both aminopenicillins with beta-lactamase-inhibitor as well as basic penicillins were prescribed significantly more often compared to non-refugees. We conclude that the high percentage of prescriptions of aminopenicillins with beta-lactamase inhibitor is striking and should be further investigated.
EVALuna2:33552

Do guidelines help us to deviate from their recommendations when appropriate for the individual patient? A systematic survey of clinical practice guidelines - Morgott, Marc; Heinmüller, Stefan; Hueber, Susann; Schedlbauer, Angela; Kühlein, Thomas (Journal of Evaluation in Clinical Practice, 2019)
Rationale, aims, and objectives: Clinical practice guidelines (CPG) were introduced to summarize the best scientific evidence available. Thereby, CPG were meant to support evidence-based medicine (EBM). However, besides evidence, EBM also asks for patients' preferences and physicians' experiences to be considered when coming to therapeutic decisions. Thus, deviations from CPG recommendations are sometimes necessary when practicing EBM. We wanted to examine whether CPG support deviations from their recommendations when appropriate. For operationalization, we asked whether absolute effect sizes (AES) for benefit and/or harm of suggested therapies were provided along with the respective CPG recommendation. Methods: This systematic survey comprised the most common CPG on chronic coronary heart disease (CCHD) and type 2 diabetes mellitus (T2DM) from English- and German-speaking countries. Only CPG recommendations on pharmacotherapy were evaluated. If AES of a recommended therapy were reported, we rated how easily findable they were within the CPG. Moreover, we assessed whether the CPG provided patient information material and whether this material supplied AES allowing patients to determine the effects to be expected. Results: In the 13 CPG surveyed, 144 recommendations on pharmacotherapy were identified. For 108 recommendations (75%), no AES for benefit and/or harm were reported. Thirty-one recommendations (22%) were accompanied by one or more AES for either benefit or harm. Along with five recommendations (3%), one or more AES for both benefit and harm were given. AES were considered easy to find for three of these 36 recommendations (8%). Patient information material was provided in three of the 13 CPG (23%) accounting for AES in one occasion only. Conclusion: Current CPG on T2DM and CCHD do not sufficiently offer AES for benefits and harms of recommended therapies. Thus, they lack satisfactory information to support deviations from CPG recommendations. Consequently, CPG in their present form do not adequately facilitate EBM.
CRIS-Team Scopus Importer:2019-07-02
Keywords: abolute risk reduction; clinical decision making; evidence-based medicine; patient-centred care; practice guidelines as topic

Effectiveness of an online education program for asthma patients in general practice: study protocol for a cluster randomized controlled trial - Eck, Stefanie; Hapfelmeier, Alexander; Linde, Klaus; Schultz, Konrad; Gensichen, Jochen; Sanftenberg, Linda; Kühlein, Thomas; Stark, Stefanie; Gágyor, Ildikó; Kretzschmann, Christian; Schneider, Antonius (BMC Pulmonary Medicine, 2022)
Background: Asthma education programs (AEPs) have been shown to increase quality of life and reduce emergency treatments and hospital admissions. Despite the proven benefits, only a minority of asthma patients attend such programs. To increase the number of educated patients, an online education program (electronic AEP, eAEP) for asthma patients has been developed. The present study aims to investigate the effectiveness of the eAEP in terms of asthma knowledge, asthma control and emergency treatments in general practice settings. Methods: This is a cluster randomized controlled trial including 100 patients with bronchial asthma from 20 general practices in Bavaria, Germany. General practices will be randomly assigned to either the intervention or control group. Patients in the intervention group will receive access to the eAEP and instructions to complete this program within two weeks. Patients in the control group will receive usual care including a referral to face-to-face AEP (fAEP) by a certified primary care physician or a pulmonologist according to guideline recommendations. Furthermore, patients of both the intervention and control groups will be invited to a follow-up consultation in their general practice after completion of the eAEP and fAEP (three weeks and twelve weeks after study inclusion, respectively) to discuss any open issues. Outcomes for both groups will be assessed at baseline (t0), after two weeks (t1), three months (t2) and six months (t3). The primary outcome is the comparison of asthma knowledge gain between intervention and control groups after completion of the eAEP (two weeks after study inclusion) and fAEP (twelve weeks after study inclusion), respectively. Secondary outcomes include asthma control, frequency of emergency treatments, patient autonomy as well as attitudes towards asthma medication. Discussion: The results of the present trial will provide knowledge about the effectiveness of an online education program for asthma patients compared to usual care in primary care. Trial registration: German Clinical Trials Register (DRKS), DRKS00028805. Registered 22 April 2022.
CRIS-Team Scopus Importer:2022-12-16
Keywords: Asthma; Asthma knowledge; Cluster randomized controlled trial; Digital intervention; Patient education; Primary care; Self-management

Erfahrungen von HausärztInnen mit COVID-19 und der Pandemie – ein Survey nach der ersten Pandemiewelle im März/April 2020 - Schrader, Hanna; Borgulya, Gábor; Parisi, Sandra; Joos, Stefanie; Kaduszkiewicz, Hanna; Barzel, Anne; Raus, Christina; Sanftenberg, Linda; Kühlein, Thomas; Maun, Andy; Schmidt, Julia; Linde, Klaus; et al. (Gesundheitswesen, 2023)
Background and Objectives The first wave of the COVID-19 pandemic (Mar-Apr 2020) posed significant challenges for primary care. The goal of this study was to analyse the burden of the crisis situation as experienced by the general practitioners (GPs) at its beginning and over the course of the pandemic and to identify factors predictive of the sense of being overburdened. Methods In this cross-sectional study, a total of 6300 randomly selected GPs in four federal states of Germany were contacted per post in order to survey changes in health care they provided and their psychological burden in the context of the pandemic between August and October 2020. Results The response rate was 23%; 46% of the participants were female. At the beginning of the pandemic, 40 % of the participants experienced a high or a very high level of being overburdened; later on, it was only 10%. With increasing numbers of COVID patients, the sense of being overburdened increased, as also their perceived capability to care for COVID patients. Predictors of a sense of being overburdened were, among others, a high level of psychological stress, excessive organising efforts, poor capability to care for COVID patients, and scarce supply of protective equipment. Conclusion Despite a sense of being overburdened initially, GPs felt increasingly capable of caring for COVID patients. To help GPs in future crisis situations like this pandemic, organization of care should be simplified to the extent possible so that they can focus on patient care.
CRIS-Team Scopus Importer:2023-07-07
Keywords: COVID-19; Hausärztliche Versorgung; Pandemiebewältigung; Überforderungsgefü

Evaluation of the German living guideline “Protection against the Overuse and Underuse of Health Care” – an online survey among German GPs - Warkentin, Lisette; Scherer, Martin; Kühlein, Thomas; Pausch, Felix; Lühmann, Dagmar; Muche-Borowski, Cathleen; Hueber, Susann (BMC Primary Care, 2024)
Background: The aim of this study was to evaluate the awareness and use of the German guideline “Protection against the overuse and underuse of health care” from the general practitioners’ (GPs’) perspective. In addition, the study assessed how GPs perceive medical overuse and what solutions they have for reducing it. Methods: We performed a cross-sectional online survey with recruitment from 15.06. to 31.07.2023. Participants were members of the German College of General Practitioners and Family Physicians (DEGAM). The main outcomes were the awareness and use of the guideline. Results: The analysis included data from 626 physicians. 51% were female and the median age was 50 years. The guideline is known by 81% of the participants, 32% read it in more detail. The majority considered the guideline a helpful tool in reducing overuse (67%). Almost 90% wished to have more guidelines with clear do-not-do recommendations. Physicians indicated in mean (M) that 30.2% (SD = 19.3%) of patients ask them for medical services that they do not consider to be necessary and that M = 30.2% (SD = 18.1%) of all GP services can be attributed to medical overuse. About half of the participants thought that overuse is a moderate or major problem in their practice (52%) and in general practice overall (58%). More participants rated that it is especially a problem in specialist (87%) and inpatient care (82%). Changes in the reimbursement system, raising awareness for the problem and more evidence-based guidelines were considered helpful in mitigating overuse. Conclusions: Although the guideline is seen as a useful tool in mitigating medical overuse, there is still further potential for its implementation and utilisation. GPs see more overuse in the inpatient and outpatient specialist areas than in their area of practice. Instead of self-critically approaching the problem, the proposed strategies are aimed at the healthcare system itself.
CRIS-Team Scopus Importer:2025-02-04
Keywords: Guidelines; Overdiagnosis; Overuse; Primary care

Evidence and practice: How do primary care physicians evaluate screening interventions? A questionnaire study - Frank, Luca; Hueber, Susann; Kühlein, Thomas; Schedlbauer, Angela; Roos, Marco (Zeitschrift für Evidenz, Fortbildung und Qualitat im Gesundheitswesen, 2018)
BACKGROUND: Patients receiving a screening intervention have to be informed about risks and benefits. On the part of the physician, it requires the understanding of statistical evidence and statistical literacy. OBJECTIVES: Do general practitioners (GPs) make different recommendations on screening interventions if they only rely on statistics compared to their decisions in everyday practice? Are the decisions relying on statistics and the decisions made in everyday practice consistent with official recommendations? Does the way of presenting the numbers (table versus pictogram) affect the decision? METHODS: Online survey among German GPs. The GPs were asked to make recommendations for three different screening scenarios which were based on statistical evidence of existing screening interventions. To avoid bias, statistics were not presented in relation to the actual diseases. The numbers were presented in either a table or a pictogram. Afterwards, the GPs were asked for their recommendations on the same screening interventions in everyday practice. RESULTS: Forty-three GPs were surveyed. Compared to everyday medical practice, participants were less likely to recommend a screening intervention when being confronted with the underlying statistical evidence (F (1, 3)=104.83, p=.002, ηpartial2=.97). Most of the decisions in everyday practice were consistent with official recommendations, while their decisions relying on statistics were more likely to deviate from them (everyday practice, M=1.79, SD=0.77; scenario, M=1.44, SD=0.80; t (42)=-2.29, p=.03). The way the numbers were presented did not affect the decision (t (127)=-1.83, p=.07). CONCLUSIONS: In everyday practice, GPs' screening recommendations do not seem to be based on statistical evidence. Presumably they would be more reluctant to recommend screening interventions if they knew the statistical evidence.
EVALuna2:34417

Expectations of general practitioners on a practice based research network in Germany- a qualitative study within the Bavarian Research Practice Network (BayFoNet) - Sanftenberg, Linda; Stofella, Julia; Mayr, Katharina; Nassehi, Armin; Härdtlein, Annette; Stark, Stefanie; Kühlein, Thomas; Kurotschka, Peter Konstantin; Gágyor, Ildikò; Eck, Stefanie; Schneider, Antonius; Bößenecker, Melanie; et al. (BMC Primary Care, 2024)
Background: Despite general practitioners' (GPs') key role in Germany`s primary health care, clinical research in general practice is scarce. Clinical research is mainly conducted at inpatient facilities, although their results are rarely transferable. German GPs have no extra time or funding for research, as well as limited research training. To support clinical research in German primary health care, practice-based research networks (PBRNs) are developed. As they will be based on an active involvement of GPs, we need more information on GPs` participation-readiness. The aim of this study was to explore facilitators and barriers to participation in the Bavarian Research Practice Network (BayFoNet) from the GPs`perspective before clinical trials will be performed. Methods: We have performed semi-structured qualitative interviews with a purposive sample of 20 Bavarian GPs in 2022 under the application of the consolidated framework for implementation research (CFIR). Transcriptions were analysed according to Kuckartz` qualitative content analysis. The five domains of the CFIR framework served as initial deductive codes. Results: N = 14 interviewees already agreed to participate in BayFoNet, whereas n = 6 interviewees opted not to participate in BayFoNet at the time of data collection. Main facilitators to conduct clinical research within BayFoNet were the motivation to contribute to evidence strength and quality in general practice, professional development and training of practice staff, as well as networking. Barriers for an active participation were bad experiences with previous clinical studies and lack of resources. Conclusions: PBRNS in Germany have to be promoted and the entire practice team has to be involved at an early stage of development. Professional training of general practice staff and a living network might enhance engagement. Participatory approaches could help to develop acceptable and feasible study designs. Furthermore, PBRNs should support patient recruitment and data collection in general practices and disseminate the results of their research projects regularly to maintain GPs` engagement. Trial registration: DRKS00028805, NCT05667207.
CRIS-Team Scopus Importer:2024-01-12
Keywords: General practice; Implementation science; Participatory research; Practice based research network; Primary health care

Experiences of general practice teams and their patients with clinical research-a mixed-methods process evaluation of the Bavarian Research Practice Network (BayFoNet) - Sanftenberg, Linda; Schnaidt, Anna Lena; Eck, Stefanie; Schneider, Antonius; Bucher, Eva; Kurotschka, Peter Konstantin; Gágyor, Ildikó; Klanke, Merle; Stark, Stefanie; Kühlein, Thomas; Walter, Fabian; Roos, Marco; et al. (BMC Primary Care, 2025)
BACKGROUND: Practice-based research networks (PBRNs) have been implemented to support clinical research in German general practice since 2020. General practitioners (GPs) are often critical concerning the feasibility of clinical trials. Among others, high workload, lack of resources in GP teams and little acceptance of the trial requirements by the patients are assumed barriers. Therefore, the aim of this study was to evaluate the perspectives of the GP teams and their patients on the set up of BayFoNet during the implementation of the two pilot cluster-randomized trials to improve this collaboration on a sustainable basis. METHODS: GPs and medical assistants (MAs) were interviewed using semi-structured interviews based on the Consolidated Framework for Implementation Research. Implementation research and verbatim transcripts were analyzed using qualitative content analysis. Patient attitudes were evaluated quantitatively with questionnaires based on the theoretical domains framework using descriptive statistics. RESULTS: A total of 15 GPs and 15 MAs were interviewed, and 109 complete patient questionnaires were returned. Main facilitators for GPs' active participation in clinical research were networking as well as active participation of GP teams at different levels of the research process. Increased awareness concerning PBRNs might promote a lively network. From the GPs' perspective, lack of motivation among MAs and patients was a perceived barrier to support clinical research in general practice. MAs emphasized their own increase in knowledge and competence as well as the importance of clinical research for improved patient care. In contrast to the GPs, most MAs were not aware of BayFoNet as a network structure. The surveyed patients rated their own capabilities and opportunities to actively participate in the pilot studies as very good. Prior to the implementations of the interventions, some patients experienced some difficulty in defining clear goals for their own participation. DISCUSSION: Increased awareness concerning PBRNs might promote a lively network. Target-group specific dissemination strategies as well as opportunities for GP teams and their patients to participate in clinical research should be elaborated. This might increase the feasibility of clinical trials and the motivation of all participants to conduct clinical trials in general practice. TRIAL REGISTRATION: Pilot cluster-randomized trial 1 (MicUTI) was prospectively registered on December 19, 2022 at www. CLINICALTRIALS: gov (NCT05667207); Pilot cluster-randomized trial 2 (IMONEDA) was prospectively registered on April 22, 2022 at www.bfarm.de (DRKS00028805).
CRIS-Team Scopus Importer:2025-03-21
Keywords: General practice; Implementation science; Participatory research; Practice based research network; Primary health care

Exploring physicians and patients' perspectives for current interventions on thyroid nodules using a MCDA method - Karrer, Linda; Zhang, Shixuan; Kühlein, Thomas; Kolominsky-Rabas, Peter (Cost Effectiveness and Resource Allocation, 2021)
Background The detection of thyroid cancer has rapidly increased over last few decades without an increase in disease specific mortality. Several studies claim that the diagnose of thyroid nodules through routine ultrasound imaging is often the trigger for cascade effects leading to unnecessary follow-up over many years or to invasive treatment. The objective of this study was to explore physicians' and patients' insights and preferences regarding the current interventions on thyroid nodules. Methods An online survey was developed using a comprehensive multi-criteria decision analysis (MCDA) framework, the EVIdence based Decision-Making (EVIDEM). The EVIDEM core model used in this study encompassed 13 quantitative criteria and four qualitative criteria. Participants were asked to provide weights referring to what matters most important in general for each criterion, performance scores for appraising the interventions on thyroid nodules and their consideration of impact of contextual criteria. Normalized weights and standardized scores were combined to calculate a value contribution across all participants, additionally differences across physicians and patients' group were explored. Results 48 patients and 31 physicians were included in the analysis. The value estimate of the interventions on thyroid nodules reached 0.549 for patients' group and 0.5 was reported by the physicians' group, compared to 0.543 for all participants. The highest value contributor was 'Comparative effectiveness' (0.073 +/- 0.020). For the physicians' group, 'Comparative safety' (0.050 +/- 0.023) was given with higher value. And for the patients' group, 'Type of preventive benefits' (0.059 +/- 0.022) contributed more positively to the value estimation. 51% participants considered 'Population priorities and access' having a negative impact on the interventions of nodules.66% participants thought that the 'system capacity' had a negative impact. Conclusion Our study shows participants' preferences on each criterion, i.e., physician indicated keeping the interventions safe and effective more important, patients indicated quality of life after receiving interventions more important. Through comparison among participants, differences have been highlighted, which can make better communication between physicians and patients. This study provides a supportive decision-making for healthcare providers when they explored the interventions on thyroid nodules.
CRIS-Team WoS Importer:2021-05-21

Gefapixant in the treatment of chronic coughing - Kühlein, Thomas; Hasford, C.; Nitschmann, S. (Innere Medizin, 2023)
CRIS-Team WoS Importer:2023-03-10

Gefapixant in the treatment of chronic coughing Gefapixant bei chronischem Husten - Kühlein, Thomas; Hasford, C.; Nitschmann, S. (Zeitschrift für Allgemeinmedizin, 2023)
CRIS-Team Scopus Importer:2023-06-02

General Fracture and Osteoporosis Prophylaxis: Focus on Falls Generelle Fraktur- und Osteoporoseprophylaxe: Fokus Sturz - Thomasius, Friederike; Maus, Uwe; Niedhart, Christopher; Brabant, Thomas; Belavy, Daniel; Kühlein, Thomas (Osteologie, 2022)
Based on a systematic literature search, the S3 guideline on Prophylaxis, Diagnosis and Therapy of Osteoporosis"(AWMF register number 183-001) was completely revised. This literature search was based on predefined PICO (Patient Intervention-Comparison-Outcome) questions. Structured consensus was reached in the interdisciplinary, German-speaking expert group from Germany, Austria, and Switzerland, representing the member societies of the DVO, and in the presence of a patient representative of the Bundesselbsthilfeverband für Osteoporose e.V. (German Self-Help Association for Osteoporosis). In this article, the most important aspects of the chapter "General Fracture and Osteoporosis Prophylaxis with the focus on "Falls"are presented.
CRIS-Team Scopus Importer:2024-12-16
Keywords: fall; fracture; guideline; osteoporosis; prophylaxis

German general practitioners' self-reported management of patients with chronic depression - Wolf, Florian; Freytag, Antje; Schulz, Sven; Lehmann, Thomas; Schaffer, Susann; Vollmar, Horst Christian; Kühlein, Thomas; Gensichen, Jochen (BMC Psychiatry, 2017)
Patients with chronic depression (persisting symptoms for >=2 years) are a clinically relevant group with extensive (co)morbidity, high functional impairment and associated costs in primary care. The General Practitioner (GP) is the main health professional attending to these patients. The aim of this study was to examine the GPs' perception on managing patients with chronic depression.We performed an explorative cross-sectional study with a systematic sample of GPs in central Germany. Source of data was a written questionnaire (46 items). Descriptive analysis was carried out.Two hundred twenty (out of 1000; 22%) GPs participated. 93% of the GPs distinguish between care for patients with chronic depression and acute depressive episode. 92% would recommend psychotherapeutic co-treatment to the chronically depressed patient. 52% of GPs would favour a general restraint on antidepressants (ADs) in older chronically depressed patients (>= 75 years) whereas 40% suggest long-term pharmacotherapy. If severe physical comorbidity is present GPs would be restrictive in prescribing ADs (65%) or would urgently refer to specialist psychiatric services (40%). In case of a comorbid anxiety disorder 66% of the GPs would suggest a combined psycho- und pharmacotherapy. If a substance use disorder coexists 84% would prefer urgent referrals to specialist services.Participating GPs report awareness towards chronic depression in their patients. Physical and mental comorbidity seem to play an important role in GPs' treatment decisions.
EVALuna2:26314

Impact of the COVID-19 pandemic on people in need of care or support: protocol for a SARS-CoV-2 registry - Gensichen, Jochen; Zöllinger, Isabel; Gagyor, Ildiko; Hausen, Anita; Hölscher, Michael; Janke, Christian; Kühlein, Thomas; Nassehi, Armin; Teupser, Daniel; Arend, Florian M.; Eidenschink, Christine; Hindenburg, Dagmar; et al. (BMJ Open, 2023)
INTRODUCTION: People in need of care or support are severely affected by the COVID-19 pandemic. We lack valid data of long-term assessments. We present a register study to detect the physical and psychosocial impact of the COVID-19 pandemic on people in need of care or support in Bavaria, Germany. To describe the persons' life conditions comprehensively, we assess the perspectives and needs of the respective care teams too. Results will serve as evidence-based source to manage the pandemic and long-term prevention strategies. METHODS AND ANALYSIS: The 'Bavarian ambulatory COVID-19 Monitor' is a multicentre registry including a purposive sample of up to 1000 patient-participants across three study sites in Bavaria. The study group consists of 600 people in need of care with a positive SARS-CoV-2 PCR test. Control group 1 comprises 200 people in need of care with a negative SARS-CoV-2 PCR test, while control group 2 comprises 200 people with a positive SARS-CoV-2 PCR test but are not in need of care. We assess the clinical course of infection, psychosocial aspects and care needs using validated measures. Follow-up is every 6 months for up to 3 years. Additionally, we assess up to 400 people linked to these patient-participants (caregivers, general practitioners (GPs)) for their health and needs. Main analyses are stratified by level of care I-V (I=minor/V=most severe impairment of independence), inpatient/outpatient care setting, sex and age. We use descriptive and inferential statistics to analyse cross-sectional data and changes over time. In qualitative interviews with 60 stakeholders (people in need of care, caregivers, GPs, politicians), we explore interface problems of different functional logics, of everyday and professional perspectives. ETHICS AND DISSEMINATION: The Institutional Review Board of the University Hospital LMU Munich (#20-860) and the study sites (Universities of Wurzburg and Erlangen) approved the protocol. We disseminate the results by peer-reviewed publications, international conferences, governmental reports, etc.
CRIS-Team Scopus Importer:2023-05-26
Keywords: COVID-19; MENTAL HEALTH; PRIMARY CARE; Public health; QUALITATIVE RESEARCH; REGISTRIES

Insights on the German College of General Practitioners and Family Physicians (DEGAM) guideline addressing medical overuse. - Warkentin, Lisette; Hueber, Susann; Kühlein, Thomas; Scherer, Martin (BMJ Evidence-Based Medicine, 2024)
EVALuna2:593961

Is it possible to register the ideas, concerns and expectations behind the reason for encounter as a means of classifying patient preferences with ICPC-2? - Schrans, Diego; Boeckxstaens, Pauline; De Sutter, An; Willems, Sara; Avonts, Dirk; Christiaens, Thierry; Matthys, Jan; Kühlein, Thomas (Primary Health Care Research & Development, 2017)
Family practice aims to recognize the health problems and needs expressed by the person rather than only focusing on the disease. Documenting person-related information will facilitate both the understanding and delivery of person-focused care. Aim To explore if the patients' ideas, concerns and expectations (ICE) behind the reason for encounter (RFE) can be coded with the International Classification of Primary Care, version 2 (ICPC-2) and what kinds of codes are missing to be able to do so.In total, 613 consultations were observed, and patients' expressions of ICE were narratively recorded. These descriptions were consequently translated to ICPC codes by two researchers. Descriptions that could not be translated were qualitatively analysed in order to identify gaps in ICPC-2.In all, 613 consultations yielded 672 ICE expressions. Within the 123 that could not be coded with ICPC-2, eight categories could be defined: concern about the duration/time frame; concern about the evolution/severity; concern of being contagious or a danger to others; patient has no concern, but others do; expects a confirmation of something; expects a solution for the symptoms without specification of what it should be; expects a specific procedure; and expects that something is not done. Discussion Although many ICE can be registered with ICPC-2, adding eight new categories would capture almost all ICE.
EVALuna2:26313

Is it really always only the others who are to blame? GP’s view on medical overuse. A questionnaire study - Pausch, Maximilian; Schedlbauer, Angela; Weiss, Maren; Kühlein, Thomas; Hueber, Susann (PLoS ONE, 2020)

Klinische Qualitätssteuerung – ein praktischer Versuch in der Hausarztpraxis am Beispiel der Influenzaimpfung - Souhrada, Vera; Zrenner, Mirjam; Schaubroeck, Emmily; Roos, Marco; Kühlein, Thomas (Zeitschrift für Allgemeinmedizin, 2023)
We understand clinical quality governance (CQG) as quality management in the clinical domain. In 2020, presumably due to the coronavirus pandemic, more patients requested to be vaccinated against influenza as compared to previous years so that it became apparent that there would be a shortage for high-risk patients. To meet the problem, we started a CQG process. This article is explicitly not a research article but an exemplary description of a CQG process intended as a stimulus and for discussion. We initiated the following process: (1) evaluation of the present state, (2) patients who already had requested a vaccination were prioritized and vaccinated first, and (3) contacting via telephone and vaccination of high-risk patients not on the list. We chose patients with chronic obstructive pulmonary disease (COPD) older than 60 years as an indicator for the group of highest priority. In the beginning only 3 (8%) of our 38 patients with COPD were vaccinated against influenza. After prioritization and vaccination of the high-risk collective in the list of those who had requested to be vaccinated, 25 (66%) of our 38 patients with COPD were vaccinated. After a phone call of high-risk patients not on the list, 28 (74%) patients were vaccinated. This represents an increase of vaccination coverage from 8% to 74% which is close to the rate recommended by the World Health Organization (WHO). In times of a pandemic, family physicians occasionally have to deal with a scarcity of resources and have to develop strategies for fair resource allocation. Not only in this context is CQG worth the effort. The generation of list queries could be improved by the providers of electronic patient records.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Family medicine; Immunization; Prioritization; Quality management

Kosteneffekte durch nicht indizierte Diagnostik der Schilddrüse - Hafner, Lucas; Tomandl, Johanna; Biermann, Valeria; Tauchmann, Harald; Schöffski, Oliver; Hoyer, Stefanie; Hueber, Susann; Donnachie, Ewan; Kühlein, Thomas (Deutsche Gesellschaft für Gesundheitsökonomie 11. Jahrestagung Gesundheitsverhalten und Prävention, 2019)
Einleitung Die Inzidenz von Schilddrüsenkarzinomen ist bei konstanter Mortalität in jüngerer Vergangenheit in Deutschland stark angestiegen. Dies ist vermutlich auf verbesserte Diagnosemöglichkeiten, die zur Entdeckung zahlreicher kleiner Schilddrüsenknoten führt, die unerkannt nie als medizinisches Problem in Erscheinung getreten wären. Wir untersuchen, ob nicht indizierte Diagnostik im Schilddrüsenkontext zu invasiven Behandlungen und infolge dessen hohen Kosten führt. Konkret untersuchen wir, ob sich durch eine nicht indizierte Sonographie der Schilddrüse die ambulanten, stationären sowie pharmazeutischen Gesundheitskosten bei den betroffenen Patienten kurz und langfristig erhöhen. Methoden Auf Basis von Routinedaten aus Deutschland werden Gesundheitskostenverläufe von Patienten untersucht, deren Symptomatik zu Beginn der Studie auf eine Fehlfunktion der Schilddrüse hindeuten. Bei allen betrachteten Patienten wurde zunächst per Blutuntersuchung der TSH-Wert bestimmt, mit dessen Hilfe Anomalien der Schilddrüsenfunktion identifiziert werden können. Als Interventionsgruppe werden die Patienten betrachtet, bei denen nicht leitliniengerecht, d.h. mit nur kurzem zeitlichen Abstand, zusätzlich eine Sonographie der Schilddrüse durchgeführt wird. Als Kontrollgruppe gelten Patienten ohne oder mit leitlinienkonformer Sonographie. Um mögliche Kosteneffekte der nicht leitliniengerechten Sonographie messen zu können, wird mittels eines Matching-Verfahren sichergestellt, dass sich beide Gruppen hinsichtlich Alter, Geschlecht, Wohnort, ambulantem Behandlungsanlass sowie Morbidität nicht unterscheiden. Ergebnisse Die durchschnittlichen Kosten für schilddrüsenspezifische ambulante Leistungen sowie schilddrüsenspezifische Arzneimittel sind in der Interventionsgruppe signifikant höher als in der Kontrollgruppe. Dieser Unterschied ist auch noch mehrere Jahre nach der Intervention zu beobachten. Allerdings ist der Anteil der schilddrüsenspezifischen Kosten an den Gesamtkosten in beiden Gruppen sehr gering. Hinsichtlich der durchschnittlichen Gesamtkosten (ambulant, stationär und pharmazeutisch) zeigen sich im Analysezeitraum keine signifikant unterschiedlichen Verläufe bei Interventions- und Kontrollgruppe. Fazit Unsere Ergebnisse liefern keine Evidenz dafür, dass eine nicht indizierte Sonographie der Schilddrüse Behandlungskaskaden auslöst, welche zu hohen allgemeinen Gesundheitskosten führt. Lediglich schilddrüsenspezifische Kosten sind nach der nicht indizierten Diagnostik selbst langfristig höher. Im Hinblick auf die Gesamtkosten fällt dieser Kostenunterschied allerdings nicht ins Gewich
Keywords: Gesundheitsökonomische Evaluation; Medizinische Überversorgung; Schilddrüsenerkrankungen

Laying the foundation for a core set of the International Classification of Functioning, Disability and Health for community-dwelling adults aged 75 years and above in general practice: a study protocol - Tomandl, Johanna; Book, Stephanie; Gotthardt, Susann; Heinmüller, Stefan; Grässel, Elmar; Freiberger, Ellen; Kühlein, Thomas; Hueber, Susann; Hoyer, Stefanie (BMJ Open, 2018)
Introduction With the medical focus on disease, the problem of overdiagnosis inevitably increases with ageing. Considering the functional health of patients might help to discriminate between necessary and unnecessary medicine. The International Classification of Functioning, Disability and Health (ICF) is an internationally recognised tool for describing functional health. However, it is too detailed to be used in primary care practices. Consequently, the aim of this study is to identify relevant codes for an ICF core set for community-dwelling older adults (75 years and above) in primary care. Methods and analysis The study will follow the methodology proposed by the ICF Research Branch to identify relevant concepts from different perspectives: (1) Research perspective: A systematic review of studies focusing on functional health in old age will be conducted in different databases. Relevant concepts will be extracted from the publications. (2) Patients' perspective: Relevant areas of functioning and disability will be identified conducting qualitative interviews and focus groups with community-dwelling older persons. The interviews will be transcribed verbatim and analysed using the documentary method of interpretation. (3) Experts' perspective: An online survey with open-ended questions will be conducted. Answers will be analysed using the qualitative content analysis of Mayring. (4) Clinical perspective: A cross-sectional empirical study will be performed to assess the health status of community-dwelling older adults using the extended ICF checklist and other measurement tools. Relevant concepts identified in each study will be linked to ICF categories resulting in four preliminary core sets. Ethics and dissemination Ethical approval for the study was obtained (90_17B). All participants will provide written informed consent. Data will be pseudonymised for analysis. Results will be disseminated by conference presentations and journal publications. Trial registration number Projektdatenbank Versorgungsforschung Deutschland: VfD_17_003833, Clinicaltrials.gov: NCT03384732 and PROSPERO: CRD42017067784.
EVALuna2:35588

Laying the foundation for a Core Set of the International Classification of Functioning, Disability and Health for community-dwelling older adults in primary care: Relevant categories of their functioning from the research perspective, a scoping review - Tomandl, Johanna; Heinmüller, Stefan; Selb, Melissa; Grässel, Elmar; Freiberger, Ellen; Kühlein, Thomas; Hueber, Susann; Book, Stephanie; Gotthardt, Susann (BMJ Open, 2021)
Objectives The objective of this study was to find relevant concepts of functioning in community-dwelling older adults within frequently used assessment instruments published in the scientific literature. This was part of a larger project to develop an International Classification of Functioning, Disability and Health (ICF) Core Set for use in primary care. Design A scoping review was conducted. Articles dealing with functioning in older adults were searched and assessed for eligibility. The study population included community-dwelling adults (≥75 years) without dementia, living in high-resource countries. Relevant concepts were extracted from assessment instruments and linked to the ICF using standardised linking rules. Finally, a frequency analysis was conducted. Setting Home, primary care. Participants Community-dwelling adults aged 75 years and above. Results From 5060 identified publications, 68 were included and 30 assessment instruments extracted. Overall, 1182 concepts were retrieved. Most were linked to the â € activities and participation' component. The most frequently identified categories were â € memory functions', â € dressing' and â € changing basic body position'. Conclusions This review provides a list of relevant ICF categories from the research perspective that will be used for developing an ICF Core Set for older primary care patients.
CRIS-Team Scopus Importer:2021-03-05
Keywords: general medicine (see internal medicine); geriatric medicine; primary care

Laying the foundation for an ICF core set for community dwelling older adults in primary care: an expert survey Entwicklung eines ICF-Core-Sets für ältere Patienten in der Hausarztpraxis: eine Expertenumfrage - Gotthardt, Susann; Tomandl, Johanna; Höfle, Anina; Kühlein, Thomas; Book, Stephanie; Graessel, Elmar; Talaska, Michael; Sieber, Cornel; Freiberger, Ellen (Zeitschrift für Gerontologie und Geriatrie, 2021)
Background: A holistic biopsychosocial model focused on functioning in individual contexts (environment, task) is better suited to meet the needs of older patients than disease only based models. The International Classification of Functioning, Disability and Health (ICF) is the official standard for describing functional health. As the ICF is too detailed to be used in practice, brief core sets have been developed. Objective: This study aimed to identify relevant aspects of functioning for older primary care patients from the perspective of healthcare professionals in Germany. Material and methods: An internet-based cross-sectional expert survey was conducted in preparation for the development of an ICF core set for community-dwelling patients aged 75 years and older. Open-ended questions to identify the most important aspects of functioning and disability in old age were used. Responses were analyzed based on a content analysis approach to identify relevant concepts in the care of the target population. These concepts were then linked to ICF categories according to established linking rules. Results: A total of 63 experts participated in this survey. Across all responses, 2240 meaningful concepts were identified. A total of 75 ICF categories (4 first level categories, 67 second level categories, 4 code combinations) were identified by at least 5% of respondents and will thus be considered as candidate categories for the final ICF core set. Most of concepts were associated with the environmental factors component. The most frequently identified categories were immediate family and family relationships. Conclusion: This survey provides a list of relevant ICF categories from the experts’ perspective and together with other preparatory studies will be used for developing an ICF core set for community-dwelling older adults in primary care.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Community-dwelling older patients; Expert survey; Functioning; ICF core set; Primary care

Laying the foundation for an International Classification of Functioning, Disability and Health Core Set for community-dwelling elderly adults in primary care: the clinical perspective identified in a cross-sectional study - Book, Stephanie; Ulbrecht, Gudrun; Tomandl, Johanna; Kühlein, Thomas; Gotthardt, Susann; Freiberger, Ellen; Grässel, Elmar (BMJ Open, 2020)
OBJECTIVES: Having more information about the biopsychosocial functioning of their geriatric patients might help physicians better balance medical interventions according to patients' needs. For this reason, we aimed to develop an easy-to-handle International Classification of Functioning, Disability and Health (ICF) Core Set for community-dwelling geriatric patients aged 75 and older in primary care. In this empirical study, we describe the functioning and health of community-dwelling patients aged 75 and older in primary care in Germany and identify the most common problems encountered by these individuals when using the ICF. DESIGN: In this exploratory, cross-sectional study, a health professional conducted semi-structured interviews. SETTING: Community-dwelling older adults aged 75 and older in Germany. PARTICIPANTS: 65 participants (mean age=80.2, SD=3.6). OUTCOME MEASURES: Extended ICF Checklist V.2.1a, patients prioritised chapters of the 'activities and participation' component. RESULTS: The three most common impairments for 'body functions' were visual system functions (ICF-code b210; 89%), blood pressure functions (b420; 80%) and sensations associated with hearing and vestibular functions (b240; 59%). For 'body structures', they were eyes, ears and related structures (s2; 81%), structure of mouth (s320; 74%) and structures related to the digestive, metabolic and endocrine systems (s5; 49%). For the 'activities and participation' component, adequate aids compensated for activity limitations to a certain degree. Still, after having adequate aids, the category in which the participants had the most difficulty was walking (d450; 35%). Participants rated the 'mobility' chapter as the most important of all chapters. 'Environmental factors' were facilitators of participants' functioning. CONCLUSIONS: This empirical study provides a list of ICF categories relevant to older adults from the clinical perspective. Along with lists from the other three preparatory studies, it will form the basis for the development of an ICF Core Set for community-dwelling older adults in primary care. TRIAL REGISTRATION DETAILS: The trial is registered in ClinicalTrials.gov (NCT03384732).
CRIS-Team Scopus Importer:2020-12-04
Keywords: aging; community-dwelling older people; core set; functioning; general practice; ICF

Laying the foundation for a primary care core set of the international classification of functioning, disability and health (icf) for community-dwelling older adults: A qualitative study - Tomandl, Johanna; Book, Stephanie; Höfle, Anina; Grässel, Elmar; Sieber, Cornel; Freiberger, Ellen; Kühlein, Thomas; Hueber, Susann; Gotthardt, Susann (Journal of Rehabilitation Medicine, 2021)
Objective: To explore relevant areas of functioning from the perspective of community-dwelling adults aged 75 years and over, in order to develop a Core Set of the International Classification of Functioning, Disability and Health (ICF) for community-dwelling older adults for use in primary care. Design: Qualitative study using semi-structured interviews and focus groups. Participants: A total of 27 community-dwelling older adults participated in the interviews and 24 of them in the focus groups. Methods: Following the proposed methodology of the ICF Research Branch, this is 1 of 4 preparatory studies in the Core Set development process. Within the transcripts, concepts of functioning were identified, based on Mayring s qualitative content analysis using deductive category assignment with the ICF being the category system. Results: Overall 6,667 concepts were identified. Most were linked to the Activities and Participation component. The most frequently identified categories were "recreation and leisure" and "family relationships". Conclusion: Categories from all ICF chapters were identified, demonstrating the complexity and multidimensionality of the ageing process, with a special emphasis on the component Activities and Participation. This qualitative study provides a list of relevant categories from the perspective of community-dwelling elderly people, which will be used to develop a Core Set for older primary care patients.
CRIS-Team Scopus Importer:2021-03-26
Keywords: aged; cross-sectional study; Disability and Health; focus group; general practice/methods.; geriatric assessment/ methods; independent living; International Classification of Functioning; interviews as topic

Leitlinien: Die Kunst des Abweichens - Kühlein, Thomas; Schaefer, Corinna (Deutsches Ärzteblatt international, 2020)
CRIS-Team Scopus Importer:2020-10-02

Medical overuse and quaternary prevention in primary care - A qualitative study with general practitioners - Alber, Kathrin; Kühlein, Thomas; Schedlbauer, Angela; Schaffer, Susann (Bmc Family Practice, 2017)
Medical overuse is a topic of growing interest in health care systems and especially in primary care. It comprises both over investigation and overtreatment. Quaternary prevention strategies aim at protecting patients from unnecessary or harmful medicine. The objective of this study was to gain a deeper understanding of relevant aspects of medical overuse in primary care from the perspective of German general practitioners (GPs). We focused on the scope, consequences and drivers of medical overuse and strategies to reduce it (=quaternary prevention).We used the qualitative Grounded Theory approach. Theoretical sampling was carried out to recruit GPs in Bavaria, Germany. We accessed the field of research through GPs with academic affiliation, recommendations by interview partners and personal contacts. They differed in terms of primary care experience, gender, region, work experience abroad, academic affiliation, type of specialist training, practice organisation and position. Qualitative in-depth face-to-face interviews with a semi-structured interview guide were conducted (n = 13). The interviews were audiotaped and transcribed verbatim. Data analysis was carried out using open and axial coding.GPs defined medical overuse as unnecessary investigations and treatment that lack patient benefit or bear the potential to cause harm. They observed that medical overuse takes place in all three German reimbursement categories: statutory health insurance, private insurance and individual health services (direct payment). GPs criticised the poor acceptance of gate-keeping in German primary care. They referred to a low-threshold referral policy and direct patient access to outpatient secondary care, leading to specialist treatment without clear medical indication. The GPs described various direct drivers of medical overuse within their direct area of influence. They also emphasised indirect drivers related to system or societal processes. The proposed strategies for reducing medical overuse included a well-founded wait-and-see approach, medical education, a trustful doctor-patient relationship, the improvement of primary/health care structures and the involvement of patients and society.GPs are frequently located at the starting point of the diagnostic and treatment process. They have the potential to play a vital role in quaternary prevention. This requires a debate going beyond the medical profession and involving society as a whole.
EVALuna2:26312

Morbidität und Inanspruchnahme des Gesundheitswesens von PatientInnen mit Verdacht auf Schilddrüsenerkrankungen. Eine retrospektive Kohortenanalyse unter Verwendung von Routinedaten. - Tomandl, Johanna; Hafner, Lucas; Biermann, Valeria; Tauchmann, Harald; Schöffski, Oliver; Hueber, Susann; Kühlein, Thomas (18. Deutscher Kongress für Versorgungsforschung, 2019)
Hintergrund In zahlreichen Ländern ist die Inzidenz von Schilddrüsenkarzinomen bei gleichbleibender Mortalität in den letzten Jahren rasant angestiegen. Dies wird als ein Indiz für Überdiagnostik gesehen. Die Entdeckung von Schilddrüsenknoten erfolgt häufig im Rahmen initial nicht indizierter Diagnostik, die dann Auslöser von Kontrollschleifen und letztlich invasiven Behandlungen sein kann. Gerade in Deutschland gibt es eine hohe Anzahl von Schilddrüsenoperationen, bei denen sich die entfernten Knoten in der anschließenden Histologie häufig als benigne herausstellen. Ziel unsere Studie ist die systematische Analyse, ob der frühzeitige Einsatz der Sonographie im Abklärungsprozess bei Verdacht auf Schilddrüsenerkrankungen in einer Art Kaskade von Überdiagnostik hin zu Übertherapie führt. Fragestellung Welche Auswirkungen hat der frühzeitige Einsatz der Schilddrüsen-Sonographie zur Abklärung von Schilddrüsenerkrankungen auf Morbidität und Inanspruchnahme des Gesundheitswesens bei den betroffenen PatientInnen? Methode Zur Beantwortung der Forschungsfrage wird aktuell eine retrospektive Kohortenanalyse mit Daten der Kassenärztlichen Vereinigung Bayerns (2012 bis 2017) durchgeführt. Untersucht werden Daten von PatientInnen mit und ohne nicht-indizierter Schilddrüsen-Sonographie. Nicht-indizierte Schilddrüsen-Sonographie wird definiert als erstmaliger TSH-Test gefolgt von einem Ultraschall der Schilddrüse innerhalb von 28 Tagen ohne Vorliegen einer Hypo- oder Hyperthyreose. Die beiden Gruppen wurden mittels Propensity Score Matching gematcht und bezüglich Morbidität und Inanspruchnahme des Gesundheitswesens untersucht. Ergebnisse Es werden Daten von 68.862 PatientInnen in jeder Gruppe ausgewertet. Die Datenanalyse ist noch nicht abgeschlossen. Die Ergebnisse werden zum Kongress vorliegen. Diskussion und praktische Implikationen Ein systematischer Vergleich verschiedener Behandlungspfade sowie deren medizinischer und ökonomischer Konsequenzen soll dazu beitragen, Überdiagnostik und Übertherapie zu identifizieren und zu beschreiben. Das Projekt wird im Rahmen des BMBF-geförderten Netzwerkes PRO PRICARE durchgeführt.
Keywords: Überversorgung; Schilddrüsenerkrankungen; Versorgungsforschung; Routinedaten; Kohortenanalyse

National Partnership for Maternal Safety: Consensus Bundle on Venous Thromboembolism - Urato, Adam C.; Abi-Jaoude, Elia; Abramson, John; Alter, Harrison; Andrew, Louise B.; Antonuccio, David; Bero, Lisa; Biron, Pierre; Boylan, Laura S.; Braillon, Alain; Brophy, James M.; Brownlee, Shannon; et al. (Obstetrics and Gynecology, 2019)
CRIS-Team WoS Importer:2020-02-28

One year of general practice during the COVID-19 pandemic - presentation and evaluation of digital medical education - van der Keylen, Piet; Zeschick, Nikoletta; Langer, Amelie; Kühlein, Thomas; Roos, Marco (GMS Journal for Medical Education, 2022)
Background and teaching situation: The SARS-CoV-2 pandemic had a substantial didactic impact on medical teaching. In Erlangen, the lecture "General Practice" was offered asynchronously and digitally in an inverted-classroom concept. Contents were available via a learning platform. The lecture was presented using annotated videos, consolidation materials and control questions. A forum encouraged for discussions and feedback and collected in-depth aspects for a case-based video consultation. The aim of this work is to evaluate and critically examine the digital teaching concept during the SARS-CoV-2 pandemic.
CRIS-Team WoS Importer:2022-09-09

Overdiagnosis and too much medicine in a world of crises - Kühlein, Thomas; Macdonald, Helen; Kramer, Barnett; Johansson, Minna; Woloshin, Steven; McCaffery, Kirsten; Brodersen, John B.; Copp, Tessa; Jørgensen, Karsten Juhl; Møller, Anne; Scherer, Martin (British Medical Journal, 2023)
CRIS-Team Scopus Importer:2023-08-25

Patient-reported reactogenicity and safety of COVID-19 vaccinations vs. comparator vaccinations: a comparative observational cohort study - Werner, Felix; Zeschick, Nikoletta; Kühlein, Thomas; Steininger, Philipp; Überla, Klaus; Kaiser, Isabelle; Sebastião, Maria; Hueber, Susann; Warkentin, Lisette (BMC Medicine, 2023)
Background: In the course of the SARS-CoV-2 pandemic, multiple vaccines were developed. Little was known about reactogenicity and safety in comparison to established vaccines, e.g. influenza, pneumococcus, or herpes zoster. Therefore, the present study aimed to compare self-reported side effects in persons vaccinated against SARS-CoV-2 with the incidence of side effects in persons receiving one of the established vaccines. Methods: A longitudinal observational study was conducted over a total of 124 days using web-based surveys. Persons receiving either a vaccination against SARS-CoV-2 or one of the established vaccines (comparator group) were included. In the first questionnaire (short-term survey), 2 weeks after vaccination, mainly local and systemic complaints were evaluated. The long-term survey (42 days after vaccination) and follow-up survey (124 weeks after vaccination) focused on medical consultations for any reason. Multivariate analyses were conducted to determine the influence of the vaccine type (SARS-CoV-2 vs. comparator) and demographic factors. Results: In total, data from 16,636 participants were included. Self-reported reactogenicity was lowest in the comparator group (53.2%) and highest in the ChAdOx1 group (85.3%). Local reactions were reported most frequently after mRNA-1273 (73.9%) and systemic reactions mainly after vector-based vaccines (79.8%). Almost all SARS-CoV-2 vaccines showed increased odds of reporting local or systemic reactions. Approximately equal proportions of participants reported medical consultations. None in the comparator group suspected a link to vaccination, while this was true for just over one in 10 in the mRNA-1273 group. The multivariate analysis showed that people with SARS-CoV-2 vaccination were not more likely to report medical consultations; patients who had received a regimen with at least one ChAdOx1 were even less likely to report medical consultations. Younger age, female gender and higher comorbidity were mostly associated with higher odds of medical consultations. Conclusion: The rate of adverse reactions after established vaccinations was roughly comparable to previous studies. Two weeks after vaccination, participants in the SARS-CoV-2 vaccination group reported more local and systemic local reactions than participants in the comparator group. In the further course, however, there were no higher odds of medical consultations in either of the two groups. Thus, altogether, we assume comparable safety. Trial registration: DRKS-ID DRKS00025881 and DRKS-ID DRKS00025373.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Adverse drug reaction; COVID-19; Medical consultation; Observational study; Reactogenicity; SARS-CoV-2; Survey; Vaccine

Physicians’ assessment of the Bavarian drug-expenditure control system: a qualitative study - Zeschick, Nikoletta; Gollnick, Julia; Muth, Julia; Hörbrand, Franziska; Killian, Peter; Donner-Banzhoff, Norbert; Kühlein, Thomas; Sebastiao, Maria (BMC Health Services Research, 2023)
Background: In 2014 a new system for drug expenditures, the Wirkstoffvereinbarung (WSV, English: Active substance agreement) was implemented in Bavaria. In pre-defined indication groups, economic prescription of medications shall be enabled based on the selection, quantity, and proportion of an individual drug. Ambulatory care physicians receive quarterly trend reports on their prescribing behavior. This study examines physicians’ perceptions of the WSV. Methods: Qualitative interviews (n = 20) and seven focus groups (n = 36) were conducted with ambulatory care physicians (e.g. general practitioners, cardiologists, pulmonologists). The methodology followed Qualitative Content Analysis. Results: Physicians generally accepted the necessity of prescribing economically. The majority of them rated the WSV positively and better than the previous system. As an improvement, they especially named timely feedback in form of easily understandable trend reports, encouraging self-reflection as well as allowing early control options. Problems perceived were drug discount contracts that were strongly criticized as leading to patients mixing up medications. Some perceived constraints of therapeutic freedom. Conclusions: The implementation of the WSV is mostly viewed positively by physicians. The restrictions of therapeutic freedom partially perceived might be met by improved information on the reasons why some drugs are rated as less economical than others. Trial registration number: Main ID: DRKS00019820 (German Register of Clinical Studies and World Health Organization).
CRIS-Team Scopus Importer:2023-09-15
Keywords: Active substance agreement; Drug costs; Drug prescriptions; Economic efficiency; Wirkstoffvereinbarung

Prescribing behavior of Bavarian general practitioners at the inpatient-outpatient interface within the context of the Bavarian active substance agreement-qualitative results of the WirtMed Study - Zeschick, Nikoletta; Gollnick, Julia; Muth, Julia; Hoerbrand, Franziska; Killian, Peter; Krombholz, Wolfgang; Donner-Banzhoff, Norbert; Kühlein, Thomas; Sebastiao, Maria (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2022)
Background and objectives In 2014, the Association of Statutory Health Insurance Physicians of Bavaria introduced the active substance agreement (WSV) for the transparent control of pharmaceutical expenditure within the framework of the efficiency principle (</n> 12 of the Fifth Book of the German Social Code [SGB V]). It replaced the prescribing target scheme. Regarding the role of the WSV, the article presents the reasons of the general practitioners (GPs) for or against a further prescription of drugs from the hospital. Materials and methods In a qualitative study design, individual interviews (n = 18) and two focus groups (n = 10) were conducted with Bavarian GPs between November 2019 and March 2020 and evaluated according to qualitative content analysis. Results With the introduction of the WSV, recourse concerns decreased for GPs overall. Patient-oriented care and the professional correctness of therapy decisions are of great importance in prescribing, ahead of cost-effectiveness. Economic challenges arise with discharge medication, especially with the lead substance target of oral anticoagulants, the generic targets for antidiabetics, and for therapeutics for the cardiovascular system. Generally criticized are drug discount contracts, which often lead to drug changes after hospital discharge. There are individual reports of a "predominance" of hospital physicians when prescribing, which is contrary to their own economic actions as GPs. According to the GPs, there is a lack of cross-sectoral cost responsibility. Conclusions In the view of GPs, a smooth interface transition is not yet available in the outpatient sector despite a framework agreement on discharge management and the new control system of the WSV. An economical supply of drugs continues to require political discussion across sectors, but also across federal states.
CRIS-Team WoS Importer:2022-07-29

Process evaluation in practice based research networks: a study protocol for a mixed-methods implementation study - Sanftenberg, Linda; Dreischulte, Tobias; Härdtlein, Annette; Kosub, Helena; Gagyor, Ildiko; Kurotschka, Peter Konstantin; Kühlein, Thomas; Burggraf, Larissa; Eck, Stefanie; Roos, Marco; Gensichen, Jochen (BMJ Open, 2023)
INTRODUCTION: General practitioners often criticise clinical trials for their poor applicability in primary care, which may at least partially explain why their engagement in primary care research remains limited. In order to enhance primary care research, the German government has funded six regional practice based research networks (PBRNs). Within the Bavarian PBRN (BayFoNet), two cluster-randomised pilot trials will be conducted. This paper presents the protocol of the process evaluation accompanying both trials, which aims to explore relevance, feasibility, acceptability and credibility of clinical research in primary care from the perspectives of BayFoNet researchers, general practitioners, and patients. METHODS AND ANALYSIS: The BayFoNet will be established by recruiting general practices (GPs) as prospective research collaborators in two cluster randomised pilot trials. Research teams will provide training in good clinical practice, and support practices in patient recruitment, data collection and documentation. Our process evaluation explores barriers and facilitators in the set up of the BayFoNet PBRN and both cluster randomised pilot trials, under the application of the consolidated framework for implementation research and the theoretical domains framework. In a mixed-methods concept, we will use qualitative and quantitative approaches to evaluate both pilot cluster-randomised trials as well as the BayFoNet itself: focus groups with researchers, semi-structured interviews with general practitioners and questionnaires for patients participating in the pilot cluster-randomised trials at three different time points. ETHICS AND DISSEMINATION: Research ethical approval for this study was granted by the Ethics Committee of the Medical Department, Ludwig-Maximilians-University Munich (AZ 21-1135). Results will be published in international peer-reviewed journals and summaries will be provided to the funders of the study as well as other PBRNs, GP teams and patients. TRIAL REGISTRATION NUMBERS: DRKS00028805, NCT05667207.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Clinical Trial; GENERAL MEDICINE (see Internal Medicine); PRIMARY CARE; QUALITATIVE RESEARCH

Protection against the overuse and underuse of health care - methodological considerations for establishing prioritization criteria and recommendations in general practice - Muche-Borowski, Cathleen; Abiry, Dorit; Wagner, Hans-Otto; Barzel, Anne; Luehmann, Dagmar; Egidi, Guenther; Kühlein, Thomas; Scherer, Martin (BMC Health Services Research, 2018)
BACKGROUND: Initiatives such as "Choosing Wisely" in the USA and "Smarter Medicine" in Switzerland have published lists of widely overused health care services. The German initiative "Choosing Wisely Together (Gemeinsam Klug Entscheiden)" follows this example. The goal of our study was to prioritize important recommendations against the overuse and underuse of health care services. The final list of recommendations will be published in the German guideline "Protection against the overuse and underuse of health care". METHODS: First, a multidisciplinary expert panel established a catalogue of prioritization criteria. Second, we extracted all the recommendations from evidence- and consensus-based German College of General Practice and Family Medicine (DEGAM) guidelines and National Health Care Guidelines (NVL). Third, the recommendations were rated by two independent panels (general practitioners and other health care professionals involved/not involved in guideline development). The prioritization process was finalized in a consensus conference held by DEGAM's Standing Guideline Committee (SLK). RESULTS: Eleven prioritization criteria were established. A total of 782 recommendations were extracted and rated by 98 physicians and other health care professionals in a survey. In the voting process, more than 80% of the recommendations were eliminated. After the final consensus conference, twelve recommendations from DEGAM guidelines, nine DEGAM addenda and 17 NVL recommendations were chosen for inclusion in the guideline, for a total of 38 recommendations. CONCLUSION: The selection procedure proved helpful in identifying the highest priority recommendations with which to combat the overuse and underuse of health care services. To date, in Germany there has been no attempt to compile such a list by using a systematic and transparent methodology. Hence, the guideline that results from this process can fill an important gap.
EVALuna2:34908

Psychological stress of general practitioners in the care of patients with palliative care needs: an exploratory study - Lopez, Verena; van der Keylen, Piet; Kühlein, Thomas; Sebastiao, Maria (BMC Palliative Care, 2024)
Background: In Germany, general practitioners play a pivotal role in palliative care provision. Caring for patients with palliative care needs can be a burden for general practitioners, highlighting the importance of self-care and mental health support. This study aimed to explore the role of palliative care in general practitioners’ daily work, the stressors they experience, their coping mechanisms, and the potential benefits of Advance Care Planning in this context. Methods: An exploratory approach was employed, combining a short quantitative survey with qualitative interviews. The analysis was based on a structuring qualitative content analysis, following a deductive-inductive procedure and integrating the Stress-Strain Model and Lazarus’ Transactional Model of Stress and Coping. We recruited eleven general practitioners to take part in the study. Results: General practitioners viewed palliative care as integral to their practice but faced challenges such as time constraints and perceived expertise gaps. Societal taboos often hindered conversations on the topic of death. Most general practitioners waited for their patients to initiate the topic. Some general practitioners viewed aspects of palliative care as potentially distressing. They used problem-focused (avoiding negative stressors, structuring their daily schedules) and emotion-focused (discussions with colleagues) coping strategies. Still, general practitioners indicated a desire for specific psychological support options. Advance Care Planning, though relatively unfamiliar, was acknowledged as valuable for end-of-life conversations. Conclusions: Palliative care can be associated with negative psychological stress for general practitioners, often coming from external factors. Despite individual coping strategies in place, it is advisable to explore concepts for professional psychological relief. Trial registration: Not registered.
CRIS-Team Scopus Importer:2024-08-16
Keywords: Advance care planning; Burden; Coping mechanism; Emotional; General practitioner; Palliative care; Stress; Stressor

Reactogenicity after heterologous and homologous COVID-19 prime-boost vaccination regimens: descriptive interim results of a comparative observational cohort study - Warkentin, Lisette; Zeschick, Nikoletta; Kühlein, Thomas; Steininger, Philipp; Überla, Klaus; Kaiser, Isabelle; Gall, Christine; Sebastiao, Maria; Hueber, Susann (BMC Infectious Diseases, 2022)
Background Due to safety signals after vaccination with COVID-19 vector vaccines, several states recommended to complete the primary immunization series in individuals having received one dose of ChAdOx1 (AstraZeneca) with an mRNA vaccine. However, data on safety and reactogenicity of this heterologous regimen are still scarce. The aim of this study was therefore to compare the reactogenicity and the frequency of medical consultations after boost vaccination in a heterologous regimen with ChAdOx1 and mRNA-vaccines (BNT162b2, BioNTech/Pfizer or mRNA-1273, Moderna) to homologous regimens with ChAdOx1 or mRNA-vaccines, respectively. Methods In an observational cohort study reactogenicity and safety were assessed 14-19 days (short-term) and 40 to 56 days (long-term) after the boost vaccination using web-based surveys. In the short-term survey solicited and unsolicited reactions were assessed, while the long-term survey focussed on health problems leading to medical consultation after the vaccination, including those that were not suspected to be vaccine-related. Results In total, 9146 participants completed at least one of the surveys (ChAdOx1/ChAdOx1: n = 552, ChAdOx1/mRNA: n = 2382, mRNA/mRNA: n = 6212). In the short-term survey, 86% with ChAdOx1/mRNA regimen reported at least one reaction, in the ChAdOx1/ChAdOx1 and mRNA/mRNA cohorts 58% and 76%, respectively (age and sex adjusted p < 0.0001). In the long-term survey, comparable proportions of individuals reported medical consultation (ChAdOx1/ChAdOx1 vs. ChAdOx1/mRNA vs. mRNA/mRNA: 15% vs. 18% vs. 16%, age and sex adjusted p = 0.398). Female gender was associated with a higher reactogenicity and more medical consultations. Younger age was associated with a higher reactogenicity, whereas elderly people reported more medical consultations. Conclusion Although the short-term reactogenicity was higher with the heterologous regimen than with the homologous regimens, other factors such as higher efficacy and limited resources during the pandemic may prevail in recommending specific regimens.
CRIS-Team WoS Importer:2022-06-17

Reactogenicity and safety of COVID-19 primary immunisation and booster vaccination regimens: a comparative observational cohort study - Warkentin, Lisette; Werner, Felix; Zeschick, Nikoletta; Kühlein, Thomas; Steininger, Philipp; Überla, Klaus; Kaiser, Isabelle; Sebastiao, Maria; Hueber, Susann (BMC Medicine, 2023)
Background: Since the beginning of the COVID-19 vaccination campaigns, recommendations regarding the vaccination have been very dynamic. Although the safety and efficacy of different vaccines have been analysed, data were scarce for vaccine regimens combining different vaccines. We therefore aimed to evaluate and compare the perceived reactogenicity and need for medical consultation after the most frequently applied homologous and heterologous COVID-19 vaccination regimens. Methods: In an observational cohort study, reactogenicity and safety were assessed within a maximum follow-up time of 124 days using web-based surveys. Reactogenicity was assessed for different vaccination regimens 2 weeks after a vaccination (short-term survey). The following surveys, long-term and follow-up surveys, focused on the utilisation of medical services, including those that were not suspected to be vaccine-related. Results: Data of 17,269 participants were analysed. The least local reactions were seen after a ChAdOx1 − ChAdOx1 regimen (32.6%, 95% CI [28.2, 37.2]) and the most after the first dose with mRNA-1273 (73.9%, 95% CI [70.5, 77.2]). Systemic reactions were least frequent in participants with a BNT162b2 booster after a homologous primary immunisation with ChAdOx1 (42.9%, 95% CI [32.1, 54.1]) and most frequent after a ChAdOx1 − mRNA-1273 (85.5%, 95% CI [82.9, 87.8]) and mRNA-1273/mRNA-1273 regimen (85.1%, 95% CI [83.2, 87.0]). In the short-term survey, the most common consequences were medication intake and sick leave (after local reactions 0% to 9.9%; after systemic reactions 4.5% to 37.9%). In the long-term and follow-up surveys, between 8.2 and 30.9% of participants reported consulting a doctor and between 0% and 5.4% seeking hospital care. The regression analyses 124 days after the first and after the third dose showed that the odds for reporting medical consultation were comparable between the vaccination regimens. Conclusions: Our analysis revealed differences in reactogenicity between the COVID-19 vaccines and vaccination regimens in Germany. The lowest reactogenicity as reported by participants was seen with BNT162b2, especially in homologous vaccination regimens. However, in all vaccination regimens reactogenicity rarely led to medical consultations. Small differences in seeking any medical consultation after 6 weeks diminished during the follow-up period. In the end, none of the vaccination regimens was associated with a higher risk for medical consultation. Trial registration: DRKS DRKS00025881 (https://drks.de/search/de/trial/DRKS00025373 ). Registered on 14 October 2021. DRKS DRKS00025373 (https://drks.de/search/de/trial/DRKS00025881 ). Registered on 21 May 2021. Registered retrospectively.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Adverse drug reaction; COVID-19; Medical consultation; Observational study; Reactogenicity; Survey; Vaccines

Referrals for uncomplicated lower back pain: A cluster parallel randomised trial of patient-centred communication to improve the management of acute back pain in primary care. A study protocol - Schedlbauer, Angela; Burggraf, Larissa; Hueber, Susann; Terzakis-Snyder, Irini-Alexia; Kühlein, Thomas; Roos, Marco (BMJ Open, 2019)
Introduction Low back pain (LBP) is one of the most frequent encounters in General Practice. Investigation and referral remain common despite the self-limiting character of episodes that are not largely attributable to specific underlying injuries. Identifying patients' ideas, concerns and expectations (ICE) is a well-established element within consultation skills training and has been shown to improve prescribing. It can be a powerful communication tool setting the base for transferring and adjusting adequate clinical information. This study aims to evaluate whether ICE can decrease unnecessary medicine in the management of acute LBP in primary care. Methods and analysis Research question: Does ICE training intervention have an effect on doctors' referrals of patients suffering from acute LBP? Population: Recruitment to this parallel cluster randomised trial will take place among general practitioners belonging to four independent practice networks in Northern Bavaria/Germany. Intervention: At baseline, 24 out of 48 doctors will be randomly assigned to take part in a 1-day training session covering theoretical background and clinical implementation of patient-centred communication by stimulating ICE. They will also be given access to a web-based supporting tool for reflective practice on their communication skills. Comparison: GPs in the control group will continue consultations as usual. Outcome: Outcome measures are referrals to diagnostic imaging, physiotherapy and specialists obtained from routine practice data, compared between intervention and control group. Time: Referrals of patients consulting their doctors for documented LBP will be monitored up to 3 months after the ICE training intervention. Ethics and dissemination Ethical approval for the study was obtained by the Ethics Committee of the University Erlangen-Nuremberg (296_17B). Results will be disseminated by conference presentations and journal publications. Trial registration number The trial is registered in clinicaltrials.gov (NCT03711071).
CRIS-Team Scopus Importer:2019-11-08
Keywords: communication; consultation; diagnosis; doctor-patient relationship; information exchange; low back pain; medical education; over investigation; primary care; shared decision-making

Reforming disease definitions: A new primary care led, people-centred approach - Moynihan, Ray; Brodersen, John; Heath, Iona; Johansson, Minna; Kühlein, Thomas; Minué-Lorenzo, Sergio; Petursson, Halfdan; Pizzanelli, Miguel; Reventlow, Susanne; Sigurdsson, Johann; Stavdal, Anna; Treadwell, Julian; et al. (BMJ Evidence-Based Medicine, 2019)
CRIS-Team Scopus Importer:2019-10-04
Keywords: public health

Schutz vor Über- und Unterversorgung – Einführung in die DEGAM-Leitlinie - Kühlein, Thomas; Egidi, Günther; Scherer, Martin; Wagner, Hans Otto; Dubben, Hans Hermann; Lühmann, Dagmar; Abiry, Dorit; Barzel, Anne; Muche-Borowski, Cathleen (Zeitschrift für Allgemeinmedizin, 2023)
Background: In June 2019, a new guideline by the German College of General Practitioners and Family Physicians (DEGAM) “Protection of medical overuse and underuse – deciding together” was published. This article echos the introduction of the guideline in a more compact and revised form. Objectives: To raise awareness of the problems of medical over- and underuse and of the existence of the guideline for a broader readership. Materials and methods: The basis of this article is the introduction and background of the guideline text, which has been revised and amended by the authors who are members of the guideline panel. Results: First medical over- and underuse are defined. Then the article introduces the reader to the causes, dimensions, and solutions of both phenomena. This includes the consequences of medical overuse for planetary health. Conclusion: Medical over- and underuse are frequent and relate to each other. The guideline offers, based on the recommendations of the other DEGAM guidelines as well as the German National Clinical Guidelines, a core set of recommendations to mitigate medical over- and underuse.
CRIS-Team Scopus Importer:2023-07-21
Keywords: General practice; Medical overuse; Overdiagnosis; Overtherapy; Planetary health

Shared decision-making in the realm of uncertainty: The example of coronary artery disease through an EBM and complexity science lens - Sturmberg, Joachim P.; Kissling, Bruno; Kühlein, Thomas (Journal of Evaluation in Clinical Practice, 2022)
Patients look to their clinicians for explanations and treatments that achieve predictable cures with certainty. Clinicians usually respond accordingly. Acknowledging uncertainty, while necessary, is difficult, anxiety-provoking and at times overwhelming for patients and clinicians alike. We here present three case studies to illustrate the uncertainties of managing patients with potentially life-threatening illnesses. Research aims to provide answers to clinical problems. But, conducting research almost inevitably entails a reduction of real-world complexities. Research ultimately can only provide 'partial or in general answers' mostly revealing new questions. Due to the complexity of clinical care, research cannot really achieve certainty and predictability for an individual within his specific living context and values. In an unavoidably uncertain environment, instead of oversimplifying, clinicians like patients-as far as possible-ought to better embrace a complexity thinking frame. This provides a deeper understanding how living bodies function as-a-whole within their living contexts. Uncertainty and unpredictability, being inherent elements of complexity thinking, cannot be overcome. However, it may be made easier to cope with uncertainty by at least adopting the thinking in probabilities for benefits and harms of patient related outcomes as introduced in Sackett's Evidence-Based Medicine framework. Through the lenses of evidence-based medicine and complexity sciences this paper critically explores the clinical management of three patients diagnosed as having coronary artery disease. They all received the same treatment even though they presented with very different clinical complaints arising from different disease manifestations. Looking at these case studies the authors reflect on the reasons behind this astonishing, but widely seen medical behaviour of 'one size fits all'. They critically reflect the importance of research and evidence in view of a person-centred solution.
CRIS-Team WoS Importer:2022-12-23

Short and medium-term cost effects of non-indicated thyroid diagnostics: Empirical evidence from German claims data - Hafner, Lucas; Biermann, Valeria; Donnachie, Ewan; Hueber, Susann; Kühlein, Thomas; Tauchmann, Harald; Tomandl, Johanna (European Journal of Health Economics, 2022)
This paper contributes to the discussion of whether non-indicated ultrasound examinations of the thyroid gland contribute to overtreatment and excess health care expenditures. Using two sources of claims data from Germany, we analyzed data from patients who underwent a TSH blood test which is the initial diagnostic measure to check for possible presence of thyroid dysfunction. In a matching analysis, we compared health costs of two groups of patients. One consisted of patients who underwent an early thyroid ultrasound that according to medical guidelines – at this point – was probably not indicated. The other group consisted of patients, who underwent no ultrasound examination at all or later in the course of the disease, making probable a correct indication. Both groups were made comparable by the means of a matching procedure. Average thyroid-specific health costs were substantially higher for the first group in the quarter in which the ultrasound examination took place. Some deviation in these specific costs persisted over a substantial period of time, with drug expenditures exhibiting the biggest difference. If, however, total health costs were considered, difference in costs was only found in the initial quarter. We conclude that non-indicated ultrasound examination of the thyroid gland may have some moderate effects on thyroid-specific costs. Yet the data do not suggest that long-lasting overtreatment and excess health expenditures are initiated by non-indicated ultrasound in German
Keywords: matching; health cost; non-indicated ultrasound; thyroid anomalies

Strukturiertes Einzelmentoring im Rahmen der Weiterbildung Allgemeinmedizin in Bayern — eine multizentrische Evaluation - Rösgen, David; Schlüssel, Sabine; Greser, Alexandra; Roos, Marco; Simmenroth, Anne; Kühlein, Thomas; Fischer, Martin; Schneider, Antonius; Lukaschek, Karoline; Schneider, Dagmar; Gensichen, Jochen (Zeitschrift für Allgemeinmedizin, 2022)
BACKGROUND: Since 2019, the competence center for specialist training in family medicine Bavaria (KWAB) offers an individual mentoring program to accompany specialist training in family medicine. The mentors are confidants for matters of specialist training, private practice, career development and compatibility of work and family life. The training takes place after registration via an online portal. METHODS: The evaluation was conducted 24 months after the start of KWAB mentoring (06/30/2021-08/01/2021). All active participants were interviewed via online survey. In each case, separate questionnaires were developed, which inquire on the one hand about the content-related aspects of the mentoring, such as topics discussed, and on the other hand about the individual mentoring relationship, such as the interpersonal relationship. The mentees received 39 questions (34 closed, 5 open) and the mentors received 26 questions (21 closed, 5 open), which were subsequently analyzed using descriptive statistics. RESULTS: N = 30 mentors and N = 72 mentees were invited to participate in the evaluation (25 (83 %) mentors and 32 (44 %) mentees participated). More than half of the participants met each other at least twice. The main methods of communication were telephone, face-to-face meetings, and email contacts. The individual time commitment in each case was judged to be appropriate. According to the mentors, the mentees showed interest in the content of the program and demonstrated availability and commitment. All respondents indicated a high level of satisfaction with one-on-one mentoring and would recommend it to others. CONCLUSIONS: Mentors and mentees in family medicine residency reported a great benefit from the one-on-one mentoring offered and a will to continue their mentoring relationships even after the project period.
EVALuna2:538461

Surveillance of drug prescribing: why outliers miss their targets – a qualitative study - Gollnick, Julia; Zeschick, Nikoletta; Hörbrand, Franziska; Killian, Peter; Sebastiao, Maria; Kühlein, Thomas; Donner-Banzhoff, Norbert (BMC Health Services Research, 2025)
Background: Rising costs are a challenge for healthcare systems. To keep expenditure for drugs under control, in many healthcare systems, drug prescribing is continuously monitored. The Bavarian Drug Agreement (German: Wirkstoffvereinbarung or WSV) for the ambulatory sector in Bavaria (the federal state of Germany) was developed for this purpose. Physicians must reach defined drug target quotas for prescribing generic drugs and certain recommended drugs specified and measured with defined daily doses (DDD). A subgroup of physicians, known as outliers, may miss their drug targets. The objective of this qualitative study was to understand the reasons physicians miss their targets. Methods: We identified outliers based on drug prescribing data from the association of statutory health insurance (SHI)-accredited physicians (KV). Outliers were invited to participate in semi-structured interviews. Results: Out of 401 outliers thus identified n = 26 physicians were interviewed. Their prescribing behaviours are affected by competing demands regarding drug decisions, such as saving staff time, costs, and discussions with patients. Often, their freedom to prescribe is limited by previous prescribers. Ease of administration of drugs not recommended also plays a role. Uncritical enthusiasm regarding the effectiveness and safety of drugs with recommendations, often reinforced by pharmaceutical marketing, leads to missed targets. Some physicians have coping strategies to avoid becoming outliers. Conclusions: Investigating physicians not meeting their targets helps us understand beliefs and barriers for appropriate drug prescribing. Based on these kinds of findings, surveillance procedures can be improved, and physicians can receive support to meet targets in the future. Trial registration: This trial has been registered in the German Register of Clinical Trials (DRKS: DRKS00016161; registration date 07. December 2018).
CRIS-Team Scopus Importer:2025-01-31
Keywords: Clinical decision-making; Drug costs; Drug prescriptions; Qualitative research; Quality of health care/economics

Telemedizin, Herzinsuffizienz und der ewige Glaube an die Technik: Eine konstruktive hausärztliche Analyse und Kritik ihrer Einführung in Deutschland - Kühlein, Thomas; Roos, Marco; Beier, Markus; Eggenwirth, Peter; Engel, Bettina; Scherer, Martin (Zeitschrift für Allgemeinmedizin, 2023)
Background: Patients with the diagnosis heart failure are frequently frail and have a poor prognosis. Now medicine is confronting them with new digital technology in the form of telemedicine with the aim of a never-ending prolongation of live, in smaller and smaller amounts. Objectives: Evaluation of the introduction of telemedicine for patients with heart failure from the perspective of primary care. Materials and methods: Summary of the scientific and non-scientific literature of the topic in a narrative review. Results: The evidence of telemedicine for heart failure is very extensive and heterogeneous. The benefit is hard to assess. The scientific basis of its introduction in Germany was reduced to a few studies which seem insufficient as a justification for it. Conclusion: An uncritical belief in technology combined with a political will based on it seems to be the real driver of this introduction. Instead of dissipating resources with more and more technology in ever smaller areas, the digitally assisted improvement of documentation and communication between patients and their primary care providers and in turn the telemedical connection and support of these by specialists might be the more appropriate answer.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Cardiology; Continuity of patient care; Politics; Primary care; Telemonitoring

The conceptualization of acute bronchitis in general practice - a fuzzy problem with consequences? A qualitative study in primary care - Schubert, Nadine; Kühlein, Thomas; Burggraf, Larissa (BMC Primary Care, 2023)
BACKGROUND: Acute bronchitis is one of the most frequent diagnoses in primary care. Scientifically, it is conceptualized as a viral infection. Still, general practitioners (GPs) often prescribe antibiotics for acute bronchitis. The explanation for this discrepancy may lie in a different conceptualization of acute bronchitis. Therefore, we wanted to know, how GPs conceptualize acute bronchitis, and how they differentiate it from common cold and pneumonia. Furthermore, we tried to find out the GPs' reasons for prescribing antibiotics in those cases. METHODS: To answer our study questions, we conducted a qualitative study with GPs in Bavaria, Germany, by using semi-structured guided interviews. The analysis of the data was conducted using the documentary method according to Ralf Bohnsack. The transcripts were subdivided into categories. Analyzing each part by reflective interpretation, first manually, secondly with the help of RQDA, we extracted the most representative citations and main messages from the interviews. RESULTS: The term acute bronchitis seems to be applied when there is neither certainty of the diagnosis common cold, nor of pneumonia. It seems it bridges the gap of uncertainty between supposedly harmless clinical pictures (common cold/viral), to the more serious ones (pneumonia/bacterial). The conceptual transitions between common cold and acute bronchitis on the one side, and acute bronchitis and pneumonia on the other are fluid. The diagnosis acute bronchitis cannot solve the problem of uncertainty but seems to be a label to overcome it by offering a way to include different factors such as severity of symptoms, presumed signs of bacterial secondary infection, comorbidities, and presumed expectations of patients. It seems to solve the pathophysiologic riddle of bacterial or viral and of decision making in prescribing antibiotics. CONCLUSION: Acute bronchitis as an "intermediate category" proved difficult to define for the GPs. Applying this diagnosis leaves GPs in abeyance of prescribing an antibiotic or not. As a consequence of this uncertainty in pathophysiologic reasoning (viral or bacterial) other clinical and social factors tip the balance towards antibiotic prescribing. Teaching physicians to better think in probabilities of outcomes instead of pathophysiologic reasoning and to deal with uncertainty might help reducing antibiotic overprescribing.
CRIS-Team Scopus Importer:2023-04-21
Keywords: Acute bronchitis; Antibiotic prescribing; Diagnostic uncertainty; Disease conceptualization; Primary care; Respiratory tract infection

'The health care system is more like a business'-medical overuse from the patients' perspective in Germany: a qualitative study - Sebastiao, Maria; Pesch, Josefine; Kühlein, Thomas; Hueber, Susann (BMJ Open, 2024)
OBJECTIVES: Medical overuse exposes patients to unnecessary risks of harm. It is an open question whether and how patients perceive the concept of medical overuse, its causes and negative consequences. DESIGN: A qualitative study design, using elements of the Grounded Theory Approach by Strauss and Corbin. SETTING: Between May 2017 and January 2020, we recruited participants and conducted face-to-face interviews in the participants' homes. Data collection took place in Bavaria, Germany. PARTICIPANTS: We recruited 16 participants (female=8, male=8) with various characteristics for the study. We used different strategies such as flyers in supermarkets, pharmacies, participants spreading information about the study or local multipliers (snowball sampling). RESULTS: The participants mostly defined medical overuse as too much being done but understood the concept superficially. During the interviews, most participants could describe examples of medical overuse. They named a variety of direct and indirect drivers with economic factors suspected to be the main driver. As a consequence of medical overuse, participants named the physical and emotional harm (eg, side effects of medication). They found it difficult to formulate concrete solutions. In general, they saw themselves more in a passive role than being responsible for bringing about change and solutions themselves. Medical overuse is a 'problem of the others'. The participants emphasised that health education is important in reducing medical overuse. CONCLUSIONS: Medical overuse was little discussed among participants, although many participants reported experiences of too much medicine. Health education and strengthening the patients' self-responsibility can play a vital role in reducing medical overuse.
CRIS-Team Scopus Importer:2024-07-26
Keywords: Decision Making; Health Services; Patients; QUALITATIVE RESEARCH; Quality in health care

“The measures taken by the government overburdened the daily practice” – insights of the PRICOV-19 study on German general practitioners in times of COVID-19 - Stark, Stefanie; Schaubroeck, Emmily; Kluge, Marie; Burggraf, Larissa; Roos, Marco; Borowski, Eve; Van Poel, Esther; Willems, Sara; Kühlein, Thomas; Hueber, Susann; Werner, Felix (BMC Primary Care, 2023)
Background: The international study PRICOV-19 aims to assess the impact of the COVID-19 pandemic on the organisation of primary health care. The German part focuses on German general practitioners during the second wave of the COVID-19 pandemic. This paper addresses the following research questions: (1) How were changes in tasks on primary care and patient treatment perceived by GPs?, (2) What was the role of GPs during the pandemic, and how was their wellbeing?, (3) How did GPs perceive health policy measures?, and, (4) What influenced the attitudes of GPs on health policy measures? Methods: This study pursues a multi-country cross-sectional design. Data collection took place throughout Germany from 01.02. to 28.02.2021 with a quantitative online questionnaire consisting of 53 items. The questionnaire was analysed through descriptive and inferential analyses using correlation and multiple regression models. Results: The response rate was 20.4% (n = 349). The respondents were mainly GPs (59.6%) in single practices (62.5%) with a mean work experience of 15 to 20 years. GPs experienced a change in their work and practice organisation (80.3%). They felt a high responsibility (70.6%) and found their work has become more meaningful to them (76%). They also saw a lack of political support (75.2%) and that the measures taken by the government overburdened the daily practice (66.4%). Not many GPs were at risk of being distressed (53.4%) but rated the health policies rather negatively (60%). The multiple regression showed, the more GPs were exposed to risk of distress, the worse they assessed the government's measures. Conclusion: GPs perceived their work as relevant and felt confident they could fulfil their tasks, but noticed that health policy initially hardly supported the outpatient sector. Health policies should increase their competence in relation to primary care, ensure its needs and consider an active inclusion of GPs in preparedness plans.
CRIS-Team Scopus Importer:2023-10-20
Keywords: COVID-19; General practitioners; Health policy; PRICOV-19; Primary health care; Quality of care; Wellbeing

The need for a change in medical research thinking. Eco-systemic research frames are better suited to explore patterned disease behaviors - Sturmberg, Joachim P.; Martin, Jennifer H.; Tramonti, Francesco; Kühlein, Thomas (Frontiers in Medicine, 2024)
Many practicing physicians struggle to properly evaluate clinical research studies – they either simply do not know them, regard the reported findings as ‘truth’ since they were reported in a ‘reputable’ journal and blindly implement these interventions, or they disregard them as having little pragmatic impact or relevance to their daily clinical work. Three aspects for the latter are highlighted: study populations rarely reflect their practice population, the absolute average benefits on specific outcomes in most controlled studies, while statistically significant, are so small that they are pragmatically irrelevant, and overall mortality between the intervention and control groups are unaffected. These observations underscore the need to rethink our research approaches in the clinical context – moving from the predominant reductionist to an eco-systemic research approach will lead to knowledge better suited to clinical decision-making for an individual patient as it takes into account the complex interplay of multi-level variables that impact health outcomes in the real-world setting.
CRIS-Team Scopus Importer:2024-06-28
Keywords: complexity science; complexity thinking; evidence-based medicine; philosophy of medicine; philosophy of science; research design; systems thinking; uncertainty

The quality of COPD care in German general practice—A cross-sectional study - Heinmüller, Stefan; Schaubroeck, Emmily; Frank, Luca; Höfle, Anina; Höfle, Anina; Langer, Michael; Saggau, Korbinian; Schedlbauer, Angela; Kühlein, Thomas (Chronic Respiratory Disease, 2020)
Objectives: Chronic Obstructive Pulmonary Disease (COPD) is a common health problem to be dealt with in primary care. Little is known about the quality of care provided for patients with COPD in Germany. Therefore, we wanted to assess the current quality of care delivered by a primary care network (PCN) for patients with COPD. Methods: A cross-sectional study was conducted in collaboration with a primary care network (PCN). All patients of the PCN aged 40 years and older with a diagnosis of COPD were identified through electronic health records (EHR). A set of quality indicators (QIs) developed in accordance with current COPD-guidelines were appraised through numerical data retrieved from the EHR. Results: In total, 2,568 patients with COPD were identified. Their mean age was 67 (SD±12) years, 49% were male. Thirty-five percent had a parallel diagnosis of asthma. There was no documentation of any spirometry for 54% of patients; 29% had a spirometry within the previous year. An influenza vaccination was documented for 37% within the preceding 12 months; 12% received a pneumococcal vaccination in the last 6 years. Smoking status was documented for 44% within the last year. Conclusion: The quality of care for patients with COPD in the PCN seemed suboptimal, despite the presence of a Disease Management Program (DMP). This finding is likely to apply widely to German general practice. Quality assessment through currently available EHR data was challenging due to non-standardized and insufficient documentation.
CRIS-Team Scopus Importer:2020-12-11
Keywords: chronic obstructive; documentation; general practice; practice guideline; Pulmonary disease; quality of health care

The search for person-related information in general practice: a qualitative study - Schrans, Diego; Avonts, Dirk; Christiaens, Thierry; Willems, Sara; De Smet, Kaat; Van Boven, Kees; Boeckxstaens, Pauline; Kühlein, Thomas (Family Practice, 2016)
BACKGROUND: General practice is person-focused. Contextual information influences the clinical decision-making process in primary care. Currently, person-related information (PeRI) is neither recorded in a systematic way nor coded in the electronic medical record (EMR), and therefore not usable for scientific use. AIM: To search for classes of PeRI influencing the process of care. METHODS: GPs, from nine countries worldwide, were asked to write down narrative case histories where personal factors played a role in decision-making. In an inductive process, the case histories were consecutively coded according to classes of PeRI. The classes found were deductively applied to the following cases and refined, until saturation was reached. Then, the classes were grouped into code-families and further clustered into domains. RESULTS: The inductive analysis of 32 case histories resulted in 33 defined PeRI codes, classifying all personal-related information in the cases. The 33 codes were grouped in the following seven mutually exclusive code-families: 'aspects between patient and formal care provider', 'social environment and family', 'functioning/behaviour', 'life history/non-medical experiences', 'personal medical information', 'socio-demographics' and 'work-/employment-related information'. The code-families were clustered into four domains: 'social environment and extended family', 'medicine', 'individual' and 'work and employment'. CONCLUSION: As PeRI is used in the process of decision-making, it should be part of the EMR. The PeRI classes we identified might form the basis of a new contextual classification mainly for research purposes. This might help to create evidence of the person-centredness of general practice.
EVALuna2:33551

The "Seminartage Weiterbildung Allgemeinmedizin" (SemiWAM (R)) - development, implementation and evaluation of a five-year, competence-based postgraduate programme in Bavaria - Roos, Marco; Schneider, Antonius; Gensichen, Jochen; Simmenroth, Anne; Kühlein, Thomas; Schneider, Dagmar (GMS Journal for Medical Education, 2022)
Introduction: Starting in 2013, a five-year, competence-based postgraduate programme, the "Seminartage Weiterbildung Allgemeinmedizin" (SemiWAM (R)) for continuing education in general practice, was developed and offered in Bavaria. This evaluation reports on the experiences of SemiWAM (R) after a first cycle.
CRIS-Team WoS Importer:2022-05-20

Treatment thresholds and minimal clinically important effect sizes of antiosteoporotic medication–Survey among physicians and lay persons in Germany - van der Keylen, Piet; Zeschick, Nikoletta; Schlenz, Anna; Kühlein, Thomas (PLoS ONE, 2022)
Background Patient decisions to take preventative treatments for osteoporosis depend on their perceptions of fracture risk, medication effect sizes (ES) of benefits and harms. However, physicians and lay persons may have differing perceptions of risks and medication efficacy. Both tend to overestimate medication benefits. This study surveyed at what risk physicians would prescribe and lay persons would be willing to take bisphosphonates, the minimum ES both groups do demand and the physicians estimates of the actual benefit of bisphosphonates. Design Cross-sectional online questionnaire survey. Methods Respondents were confronted with a case vignette with an osteoporotic patient (10-year femoral fracture risk: 32%). They were asked at what threshold of 10-year-risk of femoral neck fracture they would prescribe or take a drug. They were asked for the minimum ES (absolute risk reduction, ARR) they demand from bisphosphonates to prescribe or take them. Physicians were asked to provide their estimate of the actual ARR of bisphosphonates. Results 114 physicians and 140 lay persons answered (convenience sample/snowball distribution). The 10-year-risk threshold of lay persons (Mdnlay = 60%) willing to take medication was twice as high as the physicians’ threshold (Mdnphy = 30%) to prescribe it (p < .001). The median minimum ARR physicians demanded for bisphosphonates prescription was 17%, whereas lay persons demanded 22% (p < .001). Physicians estimated the actual ARR of bisphosphonates to be 12%. This estimated effect size was below their own minimum threshold for prescription. Conclusions Lay persons tolerate a higher fracture risk and demand a larger benefit of antiosteoporotic medication for fracture prevention than physicians. Physicians demand higher minimum benefits than their own estimates which in turn are above the benefit evidence suggests. Physicians should be more familiar with ES of antiosteoporotic drugs concerning patient outcomes and actively advise lay persons before preventive treatment decisions are taken.
CRIS-Team Scopus Importer:2022-09-02

Überversorgung durch nicht-indizierten Ultraschall der Schilddrüse? Eine Analyse von Routinedaten der Kassenärztlichen Vereinigung Bayerns - Hueber, Susann; Tomandl, Johanna; Hafner, Lucas; Biermann, Valeria; Tauchmann, Harald; Schöffski, Oliver; Lehmann, Maria; Schedlbauer, Angela; Gerlach, Roman; Tauscher, Martin; Donnachie, Ewan; Kühlein, Thomas (53. Kongress für Allgemeinmedizin und Familienmedizin (DEGAM), 2019)
Hintergrund Ein Ultraschallscreening auf Schilddrüsenerkrankungen bei symptomfreien Patienten gilt als möglicher Auslöser für Überversorgung, weshalb es nicht empfohlen wird. Wir vermuten, dass ein „graues“ Ultraschallscreening Kaskadeneffekte auslösen kann. Kaskadeneffekte sind definiert als eine Kette diagnostischer und therapeutischer Maßnahmen, die einmal begonnen nur schwer unterbrochen werden kann. Ziel unseres Projektes ist es, solche Kaskadeneffekte zu identifizieren und zu beschreiben. Fragestellung Welche Patienten sind von Kaskadeneffekten besonders betroffen? Gibt es Subgruppen mit unterschiedlichen Behandlungsverläufen? Wie unterscheiden sich diese Gruppen? Methoden Retrospektive Analyse eines Datensatzes der Kassenärztlichen Vereinigung Bayerns (2012 bis 2017). Untersucht werden Daten von Patienten mit nicht-indiziertem Schilddrüsen-Ultraschall, definiert als erstmaliger TSH-Test ohne die Diagnose einer Funktionsstörung, gefolgt von einem Ultraschall der Schilddrüse innerhalb von 28 Tagen. Um Subgruppen zu identifizieren wird eine Clusteranalyse nach der Häufigkeit von schilddrüsenspezifischen Untersuchungen im Zeitverlauf durchgeführt. Ergebnisse Es werden Daten von 41.065 Patienten ausgewertet. Erste Analysen lassen vermuten, dass es Subgruppen von Patienten gibt, die häufigen Kontrolluntersuchungen unterzogen werden. Die Datenanalyse ist noch nicht abgeschlossen. Vollständige Ergebnisse werden zum Kongress vorliegen. Diskussion Eine systematische Analyse und Darstellung von Überversorgungsprozessen, ausgelöst durch nicht-indizierte Untersuchungen, soll dazu beitragen, unnötige Medizin zu reduzieren. Das Projekt wird im Rahmen des BMBF-geförderten Netzwerkes PRO PRICARE durchgeführt. Take Home Message für die Praxis Die ersten Ergebnisse lassen vermuten, dass das Durchführen einer nicht indizierten Schilddrüsensonographie in bestimmen Patientengruppen zu Kaskadeneffekten und Überversorgung führen kan
Keywords: Überversorgung; Schilddrüse; Routinedaten; Versorgungsforschung

Vitamin-K-antagonist phenprocoumon versus direct oral anticoagulants in patients with atrial fibrillation: a real-world analysis of German claims data - Warkentin, Lisette; Klohn, Florian; Deiters, Barthold; Kühlein, Thomas; Hueber, Susann (BMJ Open, 2023)
OBJECTIVES: Direct oral anticoagulants (DOACs) were introduced based on randomised controlled trials (RCTs) comparing them to vitamin-K-antagonist (VKA) warfarin. In Germany, almost exclusively phenprocoumon is used as VKA. RCTs with phenprocoumon being absent we analysed the benefits and harms of DOACs and phenprocoumon for patients with atrial fibrillation (AF) in a real-world setting. DESIGN: In a retrospective observational cohort study, claims data covering inpatient and outpatient care from 2015 to 2019 were analysed by Cox regression and propensity score matching (PSM). SETTING: Data from a group of small-sized to medium-sized health insurance companies in Germany. PARTICIPANTS: We analysed datasets of 71 961 patients with AF and first prescription of phenprocoumon (n=20 179) or DOAC in standard dose (n=51 782). Patients with reduced dose of DOACs were excluded (n=21 724). OUTCOME MEASURES: Outcomes were thromboembolic events, major bleeding and death during a 12-month follow-up period. RESULTS: The regression analysis widely showed similarity between phenprocoumon and standard dose DOACs regarding effectiveness and safety. There were only three statistically significant differences: a lower bleeding risk with composite DOACs and apixaban (HR (95% CI) = 0.67 (0.59 to 0.76) and 0.54 (0.46 to 0.63), respectively) and a higher risk of death with rivaroxaban (1.21 (1.10 to 2.34)). The analysis after PSM was consistent with the first two results regarding composite DOACs and apixaban (number needed to treat, NNT 101 and 78) and showed a lower bleeding risk with rivaroxaban (NNT 156). Absolute differences were small. CONCLUSIONS: The small superiority or non-inferiority of DOACs over warfarin seen in the RCTs might not translate into relevant advantages of DOACs over phenprocoumon. To confirm the hypothesis, an RCT with phenprocoumon is needed. Next to the safety and effectiveness assessments other factors might also play a substantial role in the decision on the right OAC for stroke prevention.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Anticoagulation; Cardiology; CLINICAL PHARMACOLOGY; GENERAL MEDICINE (see Internal Medicine); Stroke

Vitamin-K-antagonist phenprocoumon versus low-dose direct oral anticoagulants (DOACs) in patients with atrial fibrillation: a real-world analysis of German claims data - Warkentin, Lisette; Hueber, Susann; Deiters, Barthold; Klohn, Florian; Kühlein, Thomas (Thrombosis Journal, 2022)
Background For stroke prevention in patients with atrial fibrillation (AF), direct oral anticoagulants (DOACs) have been increasingly prescribed instead of vitamin-K-antagonists (VKA). For some patients a lower dosage of DOACs (ld-DOACs) is recommended. Ld-DOAC prescribing seems to be common, although previous studies did not show clear superiority of ld-DOACs over warfarin. In Germany, phenprocoumon is used almost exclusively as VKA. Randomized controlled trials comparing DOACs and phenprocoumon in the general population of patients with AF do not exist. Therefore, we aimed to compare ld-DOACs and phenprocoumon in a real-world setting in Germany. Methods In a retrospective observational cohort study, claims data from a group of small to medium-sized health insurance companies were analysed. Risks for the outcomes thromboembolism, death and major bleeding were estimated by Cox regression. Out of 93,685 patients with atrial fibrillation and a first prescription of an oral anticoagulant, 20,179 receiving VKA and 21,724 ld-DOACs (29.6% of all DOAC patients) were included. For the sensitivity analysis phenprocoumon was compared to the five ld-DOAC groups (ld-apixaban, ld-dabigatran, ld-edoxaban, ld-rivaroxaban, and the composite of all ld-DOACs) after propensity-score matching. Results Phenprocoumon was associated with statistically significant fewer thromboembolic events (HR = 1.29, 95% CI [1.13, 1.48], p < .001) and deaths (HR = 1.52, 95% CI [1.41, 1.63], p < .001) and a non-significant higher bleeding risk (HR = 0.89, 95% CI [0.79, 1.00], p = .051) than composite ld-DOAC. Regarding the subgroups, only patients with ld-apixaban had a statistically significant higher risk for thromboembolic events (HR = 1.42, 95% CI [1.21, 1.65], p < .001) and a lower bleeding risk (HR = 0.75, 95% CI [0.65, 0.86], p < .001). Ld-apixaban, ld-edoxaban, and ld-rivaroxaban were associated with a higher risk of death. The sensitivity analysis confirmed these associations. Conclusion Phenprocoumon seems to be superior to ld-DOACs for patients with AF. As a hypothesis phenprocoumon might turn out to be the wiser choice for high-risk patients with AF as compared to ld-DOACs, especially regarding thromboembolic events and death. Therefore, RCTs comparing ld-DOACs with phenprocoumon are needed.
CRIS-Team WoS Importer:2022-06-10
Keywords: Direct oral anticoagulants; Phenprocoumon; Vitamin-K-antagonists; Atrial fibrillation; Low-dose therapy

Was bedeutet ärztliche Professionalität? - Kühlein, Thomas (Zeitschrift für Allgemeinmedizin, 2020)
There is a tacit contract between medicine and society. The essence of this contract is professionalism. But while most physicians know the rules of professional behavior towards the patient by the Declaration of Geneva, few know those towards society. This is why the topic of the 53. Conference of the German College of General Practitioners and Family Physicians (DEGAM) in Erlangen was chosen to be “The work of the general practitioner between patient welfare and claims of society – What does medical professionalism mean?” This article relates to the keynote lecture held at the beginning of the conference.
CRIS-Team Scopus Importer:2020-05-29
Keywords: Conference of the German College of General Practitioners and Family Physicians (DEGAM); Family physician; Keynote; Professionalism; Society

Was heißt schon normal? Was man in der hausärztlichen Praxis über Persönlichkeitsstörungen wissen sollte - Kühlein, Thomas; Hasan, Gabriel; Deinzer, Anja; Silbermann, Andrea (Zeitschrift für Allgemeinmedizin, 2024)
Personality disorders are common, and often remain undiagnosed or are hidden by other psychiatric diagnoses such as anxiety or depression. Unusual behaviors include emotional instability, self-harming behavior, and difficulty building relationships. The diagnosis should be made by a specialist in a structured manner and communicated to the patient. Especially for borderline personality disorder the benefit of specific psychotherapy is evidence based. Drug therapies with psychotropic drugs should be avoided. A change in psychiatry is currently being observed in the area of personality disorders. The old way of thinking in terms of strict disease categories is increasingly being replaced by a dimensional description of mental disorders. How quickly this will happen and whether this new approach will be more successful than the old one remains to be seen.
CRIS-Team Scopus Importer:2024-10-11
Keywords: Borderline personality disorder; Dialectical behavior therapy; Patient-centered care; Primary health care; Psychiatry

What do people know and think about medical overuse? an online questionnaire study in Germany - Nürnberger, Carolin; Kühlein, Thomas; Hueber, Susann (PLoS ONE, 2024)
Background Medical overuse is defined as health care services that exceed the individual needs of patients and when the potential harms of medical interventions exceed their benefits. It has impacts on patients as well as on health care resources. To address medical overuse, it is important to understand the knowledge and experiences of overuse on the side of patients. Research questions What is the citizens’ understanding of overuse? How do they assess its relevance, causes, consequences and potential solutions? Methods A quantitative online survey was conducted. The participants were asked to state what they understand by medical overuse. Statements on causes, consequences and possible solutions were evaluated. Recruitment was carried out via a panel of a market research institute (Schlesinger Group). Results The survey was completed by 406 participants. In terms of age and gender, the sample corresponded to the distribution in the German population. The majority had never heard of medical overuse (58%). About 60% assumed that medical overuse means "too much medicine including overtreatment and overtesting”. Medical overuse was mainly suspected for services not covered by the public health insurance system (56%), surgical interventions (45%) and medication prescriptions (37%). Reasons for medical overuse were seen in uncoordinated care and financial incentives, but also in the expectations of patients. The main problem with medical overuse was seen in rising health care costs, while harmful physical and mental consequences for patients were mentioned less often. In order to reduce medical overuse, little importance was attributed to a primary care based system or higher financial contribution of patients. Instead, stricter cost control on the side of physicians and better coordination between care providers were suggested as solutions. Differences in socio-demographic characteristics hardly showed any differences in response behavior. Conclusion More than half of the respondents had never heard of medical overuse. Overuse was mainly associated with financial causes and consequences. It was not seen that overuse can be harmful for patients directly. The limited awareness of the problem of overuse probably is a barrier to tackling it effectively. Communicating the topic to the public might therefore be an effective start to mitigate medical overuse. Take home message Many citizens seem not to be familiar with the concept of medical overuse, especially not with the fact that it may directly cause harm to patients. Informing citizens about the harms of medical overuse might be helpful in mitigating it.
CRIS-Team Scopus Importer:2024-03-22

“What else to say?”-Primary health care in times of COVID-19 from the perspective of German general practitioners: An exploratory analysis of the open text field in the PRICOV-19 study - Stark, Stefanie; Kluge, Marie; Schaubroeck, Emmily; Werner, Felix; van Poel, Esther; Willems, Sara; Roos, Marco; Kühlein, Thomas; Burggraf, Larissa (PLoS ONE, 2023)
Background The international collaboration study PRICOV-19 -Primary Health Care in times of COVID-19 aims to assess the impact of the COVID-19 pandemic on the organisation of primary health care. The German part focuses on the subjective perceptions of general practitioners on primary health care and the impact of political measures during the second wave of the COVID-19 pandemic. Within this survey, the “open text field” of the questionnaire was utilised remarkably frequently and extensively by the respondents. It became clear that the content that was named needed to be analysed in an exploratory manner. Accordingly, this paper addresses the following question: What preoccupies general practitioners in Germany during COVID-19 that we have not yet asked them enough? Methods The data collection took place throughout Germany from 01.02.2021 to 28.02.2021with a quantitative online questionnaire consisting of 53 items arranged across six topics as well as an “open text field” for further comments. The questionnaire's open text field was analysed following the premises of the qualitative content analysis. Results The topics discussed by the respondents were: insufficient support from health policies, not being prioritised and involved in the vaccination strategy, feeling insufficient prepared, that infrastructural changes and financial concerns threatened the practice, and perceiving the own role as important, as well as that health policies affected the wellbeing of the respondents. One of the main points was the way general practitioners were not sufficiently acknowledged for their contribution to ensuring high-quality care during the pandemic. Discussion German general practitioners perceived their work and role as highly relevant during the COVID-19 pandemic. In controversy with their perception, they described political conditions in which they were the ones who contributed significantly to the fight against the pandemic but were not given enough recognition.
CRIS-Team Scopus Importer:2023-03-31

"What they see is what you get": Prescribing antibiotics for respiratory tract infections in primary care: Do high prescribers diagnose differently? An analysis of German routine data - Hueber, Susann; Kühlein, Thomas; Gerlach, Roman; Tauscher, Martin; Schedlbauer, Angela (PLoS ONE, 2017)
Characteristics of high and low prescribers of antibiotics in German primary care were analysed using population data. We aimed to evaluate differences in prescribing rates and factors being associated with high prescribing, and whether high prescribers made the diagnosis of perceived bacterial infections more often.Routine data were provided by the Bavarian Association of Statutory Health Insurance Physicians. Routine data are delivered by primary care practices on a quarterly basis. We analysed data from 2011 and 2012. Patients older than 15 years with respiratory tract infections consulting a primary care physician were selected (6.647 primary care practices). Patient and physician characteristics associated with high prescribing were identified using stepwise logistic regression.Mean prescribing rate of antibiotics was 24.9%. Prescribing rate for high prescribers was 43.5% compared to 8.5% for low prescribers. High prescribers made the diagnosis of perceived bacterial infections more often (Mhigh = 64.5%, Mlow = 45.2%). In the adjusted regression model, perceived bacterial infections were strongly associated with high prescribing (OR = 13.9, 95% CI [10.2, 18.8]). Treating patients with comorbidities was associated with lower prescribing of antibiotics (OR = 0.6, 95% CI [0.4, 0.8]). High prescribers had a higher practice volume, a higher degree of prescribing dominance, and were situated more often in deprived areas and in rural settings.Compared to findings of studies in other European countries, prescribing rates were low. There was a considerable difference between prescribing rates of high and low prescribers. Diagnostic labelling was the best predictor for high prescribing. Current guidelines recommend considering antibiotic treatment for patients with co-morbidities. In our study, treating a large number of high-risk patients was not associated with high prescribing.
EVALuna2:26311

Zwischen Heilkunst und Kommerz: Welche Ökonomie verträgt „gute“ Medizin? - Blumenthal, Sandra; Donner-Banzhoff, Norbert; Popert, Uwe; Kühlein, Thomas (Zeitschrift für Allgemeinmedizin, 2021)
The economization and commercialization of patient care frequently is a subject in public discussions. In the past of this discourse ambulatory care was mostly omitted. We develop and discuss eleven theses to ensure good primary care. An economically responsible behavior as an ethical demand for the health professional is contrasted with a commercialized health care system that subordinates patient care to financial interests. The implementation of a primary care based system in Germany and ethical reflections on the medical education of students and young doctors are discussed to meet the problems of industrialization and commercialization in our health care system.
CRIS-Team Scopus Importer:2021-03-26
Keywords: Commercialization; Doctor-patient relationship; Economization; Ethical challenges in family medicine; Family medicine and medical ethics; Medicine and economics